Alloy coating, coated product, alloy coating composition, application of protective coating and preparation method

A Cr-Zr-N alloy coating with a disordered and dense structure addresses the corrosion and hardness issues of alloy materials, enhancing durability and resistance to scratches in lightweight substrates.

CN119177417APending Publication Date: 2024-12-24VITALINK INDUSTRY (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310751874.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Alloy materials used in lightweight substrates, such as those in 3C products, suffer from weak corrosion resistance and low surface hardness, limiting their application and promotion due to susceptibility to corrosion and scratches.

Method used

A Cr-Zr-N alloy coating with a highly disordered and densely packed structure, characterized by X-ray diffraction peaks within 30° to 50° and specific atomic distribution, is applied using vapor deposition, providing excellent corrosion resistance and high hardness.

Benefits of technology

The Cr-Zr-N alloy coating significantly enhances corrosion resistance, passing 24-48h salt spray tests and reducing scratch damage, while maintaining a dense structure that avoids gaps, thus improving the durability of alloy materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177417A_ABST
    Figure CN119177417A_ABST
Patent Text Reader

Abstract

The invention relates to an alloy coating, a coated product, an alloy coating composition, application of a protective coating and a preparation method. The alloy coating contains a Cr-Zr-N alloy material, an X-ray diffraction pattern of the alloy coating has a diffraction peak within the diffraction angle 2theta (degree) range of 30-50 degrees, the full width at half maximum of at least one 2theta (degree) diffraction peak within the range of 30-50 degrees is larger than or equal to 2 degrees, a radial intensity profile corresponding to a selected area electron diffraction pattern has a diffraction peak within the range of # imgabs0 #, and the maximum width at half maximum of at least one 2theta (degree) diffraction peak within the range of 30-50 degrees is larger than or equal to 2 degrees. And the full width at half maximum of at least one diffraction peak in the range of # imgabs 1 # meets # imgabs 2 #, so that the alloy coating can be formed on the surface of a coated product by adopting a corresponding alloy coating composition, and the alloy coating can be used as at least one part of a protective coating to provide excellent corrosion resistance and high hardness characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coating protection technology, and further to the field of alloy coating technology, and in particular to the application and preparation method of alloy coatings, plated products, alloy coating compositions, and protective coatings. Background Art

[0002] With the development of science and technology and the improvement of the quality of life, products in various fields such as automobile, aerospace, wearable products, 3C products, sports products, etc. are showing a trend of lightweight development. Representatively, "3C products" are a collective name for computer, communication and consumer electronic products, also known as "information appliances", such as computers, tablet computers, mobile phones or digital audio players. Since 3C products are generally not large in size, they are often collectively referred to as "3C small appliances".

[0003] Selecting a substrate of suitable material can help achieve lightweighting, such as alloy materials, pure metals and other materials. Taking alloy materials as an example, alloy materials are more and more widely used in lightweight substrates due to their low cost and lighter texture. However, alloy materials and a variety of pure metals have weak corrosion resistance and low surface hardness, and are prone to corrosion and scratches during use, which limits their promotion and application. Adding a layer of alloy protective coating on the surface of the substrate can be used to improve hardness, corrosion resistance and other problems, but the overall effect is still not ideal.

[0004] Therefore, it is of great significance to develop alloy protective coatings that have both high corrosion resistance and high hardness. Summary of the invention

[0005] Based on this, the purpose of the present invention includes providing an alloy coating, which has excellent corrosion resistance and high hardness characteristics and can be used as a protective coating or a part thereof for a plated product; in addition, an alloy coating composition constituting the alloy coating, its application in protective coatings and a method for preparing the alloy coating are also provided.

[0006] In a first aspect of the present invention, an alloy coating is provided.

[0007] The alloy coating contains a Cr-Zr-N alloy material, and the alloy coating satisfies the following two characteristics:

[0008] The X-ray diffraction pattern of the alloy coating has a peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak within the range of 30° to 50° satisfies ≥ 2°;

[0009] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating, the characteristic atomic distance is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of At least one within the range

[0010] In some embodiments, the X-ray diffraction pattern of the alloy coating satisfies one or more of the following characteristics:

[0011] The X-ray diffraction pattern of the alloy coating satisfies a half-width of all 2θ(°) diffraction peaks within a diffraction angle 2θ(°) range of 30° to 50°, which satisfies ≥2°; the X-ray diffraction pattern of the alloy coating is obtained by Cu target Kα rays.

[0012] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating satisfies one or more of the following characteristics:

[0013] The radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating is All in range

[0014] The selected area electron diffraction pattern of the alloy coating is obtained using TEM characterization technology, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

[0015] In some embodiments, the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , M is a doping element, wherein x, y, z and a are each independently an atomic ratio, 15≤x≤81.6, 12.1≤y≤78.8, 4.7≤z≤35.9, and 0≤a / (x+y+z+a)≤0.05.

[0016] In some embodiments, the sum of x, y, and z is 100.

[0017] In some embodiments, 0≤a / (x+y+z+a)≤0.02.

[0018] In some embodiments, the doping element is a non-metallic element, a metallic element, or a combination thereof;

[0019] The non-metallic elements include one or more of O, C, B, Si and Ar;

[0020] The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0021] In some embodiments, the thickness of the alloy coating is d min nm~6μm, where d min Selected from 10 nm to 50 nm.

[0022] In some embodiments, d min The thickness of the alloy coating is 1 μm to 2.5 μm.

[0023] In a second aspect of the present invention, a coated product is provided, comprising a substrate and the alloy coating according to the first aspect of the present invention; wherein the alloy coating is located on at least one side of the substrate.

[0024] In some embodiments, the surface material of the substrate is one of an alloy, a single metal, and an inorganic non-metallic material; the material type of the alloy includes one or more of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based, and zinc-based;

[0025] The elemental metal is any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium;

[0026] The inorganic non-metallic material includes one or more of ceramics and glass.

[0027] In some embodiments, the surface material of the substrate is one of light alloys or one of stainless steel alloys; wherein the light alloy includes one or more of titanium alloy, aluminum alloy and magnesium alloy.

[0028] In some embodiments, the coated article satisfies one or more of the following features:

[0029] The alloy coating is in direct contact with the substrate or is provided with a transition layer;

[0030] The alloy coating is located on the surface of the coated product or a surface layer is provided on the side of the alloy coating away from the substrate, and the surface layer is a single-layer structure or a multi-layer structure.

[0031] In some embodiments, the coated product is one of a 3C digital product, an automotive product, an aerospace product, a wearable product, and a sports product.

[0032] In a third aspect of the present invention, an alloy coating composition is provided, wherein the alloy coating composition contains a Cr—Zr—N alloy material, and the Cr—Zr—N alloy material is as defined in the first aspect of the present invention.

[0033] In one aspect of the present invention, there is also provided a Cr—Zr—N alloy material as defined in the first aspect of the present invention.

[0034] In the fourth aspect of the present invention, there is provided the use of the alloy coating described in the first aspect of the present invention as at least a part of the protective coating of a coated product, or the use of the alloy coating composition described in the third aspect of the present invention in preparing at least a part of the protective coating of a coated product.

[0035] In some embodiments, the protective coating of the coated article is a corrosion-resistant protective coating.

[0036] In the fifth aspect of the present invention, a method for preparing an alloy coating is provided, which comprises the following steps: using vapor deposition technology to deposit the constituent elements of the alloy coating on at least a portion of the surface of a substrate according to a preset atomic ratio to form the alloy coating described in the first aspect of the present invention.

[0037] In some embodiments, the method for preparing the alloy coating includes the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using one or more target materials comprising chromium and zirconium, sputtering and depositing the constituent elements of the alloy coating on at least a portion of the surface of the substrate to form the alloy coating.

[0038] In some embodiments, the preparation method satisfies any one or more of the following characteristics:

[0039] The temperature of sputtering deposition is 30℃~330℃;

[0040] The total gas pressure of the mixed gas containing argon gas and nitrogen-containing gas is 0.3Pa to 1.2Pa;

[0041] The target material includes a chromium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 , optional 1.3W / cm 2 ~6.0W / cm 2 ;

[0042] The target material includes a zirconium target, and the power density of the zirconium target is 0.5 W / cm 2 ~7.9W / cm 2 , optional 1.5W / cm 2 ~7.9W / cm 2 ;

[0043] The target material includes an alloy target, and the alloy target includes at least two metal elements in the alloy coating; optionally, the target material includes a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2 ~6W / cm 2 ;

[0044] The bias voltage of the substrate is -150V to -20V;

[0045] The sputtering deposition time is 10min to 150min;

[0046] The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 5 sccm to 52 sccm;

[0047] The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon gas to nitrogen gas in the mixed gas is (2-6):1;

[0048] The alloy coating provided by the present invention contains a Cr-Zr-N alloy material, and is therefore also a Cr-Zr-N alloy coating. The Cr-Zr-N alloy material includes at least three elements: Cr, Zr and N. The Cr-Zr-N alloy material in the alloy coating has a highly disordered atomic distribution and a sufficiently dense atomic arrangement, so that on the one hand, there is at least one 2θ (°) diffraction peak with a half-height width ≥ 2° in the range of 30° to 50° in an X-ray diffraction (XRD) diagram. On the other hand, a corresponding radial intensity profile is obtained according to a selected area electron diffraction pattern (SAED) diagram of the alloy coating, which is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the abscissa and the diffraction intensity as the ordinate. The range has at least The special microstructural feature enables the alloy coating provided by the present invention to have a highly dense structure, excellent corrosion resistance and high hardness.

[0049] Traditional Cr-Zr-N alloy coatings are usually nanocrystalline (i.e., the three atoms of Cr, Zr, and N are arranged in an orderly manner at the nanoscale), have a columnar crystal structure, and usually have a large number of through-column gaps, resulting in poor corrosion resistance and hardness characteristics. The Cr-Zr-N alloy coating provided by the present invention has a "highly disordered and fully densely packed" structure, which can reduce or avoid the large number of through-column gaps present in traditional alloy coatings, thereby greatly improving the corrosion resistance of the Cr-Zr-N alloy coating. The alloy coating provided by the present invention has excellent corrosion resistance. For example, when the alloy coating provided by the present invention is prepared on the surface of an aluminum alloy, the salt spray corrosion resistance test using the ASTM B117 salt spray test method can pass the 24h test, and most embodiments can pass the 48h test, while traditional alloy coatings are generally difficult to pass the 8h test. In addition, the high hardness characteristics of the alloy coating provided by the present invention can reduce or weaken scratch damage.

[0050] When the Cr-Zr-N alloy material in the alloy coating provided by the present invention has a more suitable element ratio, for example, 15≤x≤81.6, 12.1≤y≤78.8 and 4.7≤z≤35.9 (wherein x, y and z are the element atomic ratios of Cr, Zr and N, respectively), it is beneficial to form a denser structure and obtain better corrosion resistance.

[0051] The alloy coating provided by the present invention can have both high corrosion resistance and high hardness characteristics at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs.

[0052] The alloy coating provided by the present invention can be used as at least a part of the protective coating of the plated product. Furthermore, the alloy coating provided by the present invention can be applied to a variety of substrates, the materials of which include but are not limited to alloys, elemental metals, inorganic non-metallic materials and other substrates.

[0053] When the alloy coating provided by the present invention appears in the protective coating of the plated product, the position of the alloy coating in the protective coating of the plated product can be flexibly set. For example, the alloy coating can be used for surface protection, in which case the alloy coating is located on the surface of the plated product; the alloy coating can also be used as an intermediate protective layer, in which case other structural layers are provided on the outside of the alloy coating, that is, the alloy coating may not be used as a surface layer. Different coating position settings can achieve better scratch resistance and better corrosion resistance.

[0054] The preparation method of the alloy coating provided by the present invention is simple, easy to operate, green and environmentally friendly, and also has the advantages of being quantifiable, highly efficient and highly repeatable, and is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. It should also be noted that the drawings are all drawn in a simplified form and are only used to conveniently and clearly assist in explaining the present invention. The various sizes of each component shown in the drawings are arbitrarily shown and may be accurate or may not be drawn according to the actual scale. For example, in order to make the illustration clearer, the size of the components is appropriately exaggerated in some places in the drawings. Unless otherwise specified, the components in the figure are not drawn to scale. The present invention does not limit each size of each component.

[0056] In the following description, the same reference numerals denote the same parts.

[0057] Figure 1 A schematic diagram of an apparatus for preparing the alloy coating of the present application in one embodiment of the present invention;

[0058] Figure 2 Schematic diagrams of the structures of the coated products in several embodiments of the present invention: (A) includes a substrate and the alloy coating of the present invention; (B) includes a substrate, a transition layer and the alloy coating of the present invention; (C) includes a substrate, a transition layer, the alloy coating of the present invention and a surface layer; (D) includes a substrate, the alloy coating of the present invention and a surface layer;

[0059] Figure 3 The Cr prepared in Example 1 of the present invention 81.6 Zr 13.7 N 4.7 SEM cross-sectional image of the alloy coating;

[0060] Figure 4 The Cr prepared in Example 1 of the present invention 81.6 Zr 13.7 N 4.7 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0061] Figure 5 The Cr prepared in Example 2 of the present invention 61.4 Zr 33.2 N 5.4 SEM cross-sectional image of the alloy coating;

[0062] Figure 6 The Cr prepared in Example 2 of the present invention 61.4 Zr 33.2 N 5.4XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0063] Figure 7 The Cr prepared in Example 3 of the present invention 47.1 Zr 17.4 N 35.5 SEM cross-sectional image of the alloy coating;

[0064] Figure 8 The Cr prepared in Example 3 of the present invention 47.1 Zr 17.4 N 35.5 XRD diffraction pattern of alloy coating;

[0065] Fig. 9 The Cr prepared in Example 4 of the present invention 52.0 Zr 12.1 N 35.9 SEM cross-sectional image of the alloy coating;

[0066] Fig.10 The Cr prepared in Example 4 of the present invention 52.0 Zr 12.1 N 35.9 XRD diffraction pattern of alloy coating;

[0067] Fig.11 The Cr prepared in Example 5 of the present invention 60.9 Zr 26.1 N 13 SEM cross-sectional image of the alloy coating;

[0068] Fig.12 The Cr prepared in Example 5 of the present invention 60.9 Zr 26.1 N 13 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0069] Fig.13 The Cr prepared in Example 6 of the present invention 60.9 Zr 26.1 N 13 SEM cross-sectional image of an alloy coating, the alloy coating being the lower layer of a double-layer structure coating, and a titanium nitride coating (as a surface layer) being present above the alloy coating;

[0070] Fig.14 The Cr prepared in Example 7 of the present invention 60.9 Zr 26.1 N 13SEM cross-sectional view of the alloy coating, a Cr layer (as a transition layer) in contact with the alloy coating is provided between the substrate layer and the alloy coating, and a titanium nitride coating (as a surface layer) is also provided above the alloy coating; the coated product has a sandwich structure protection structure, and the alloy coating serves as the middle structural layer of the three-layer structural coating;

[0071] Fig.15 The Cr prepared in Example 9 of the present invention 15.0 Zr 78.8 N 6.2 SEM cross-sectional image (A), selected area electron diffraction pattern (SAED) image (B), and radial intensity profile corresponding to SEAD image (C) of the alloy coating;

[0072] Fig.16 The Cr prepared in Example 10 of the present invention 15.0 Zr 49.5 N 35.5 SEM cross-sectional image of the alloy coating;

[0073] Fig.17 The Cr prepared in Example 10 of the present invention 15.0 Zr 49.5 N 35.5 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0074] Fig.18 The Cr prepared in Example 11 of the present invention 41.3 Zr 33.2 N 25.5 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0075] Fig.19 The Cr prepared in Example 15 of the present invention 49.5 Zr 18.0 N 32.5 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0076] Fig. 20 The Cr prepared in Comparative Example 1 of the present invention 88.9 Zr 11.1 SEM cross-sectional image of the alloy coating;

[0077] Fig.21 The Cr prepared in Comparative Example 2 of the present invention 37.8 Zr 16.2 N 46SEM cross-sectional image of the alloy coating;

[0078] Fig. 22 The Cr prepared in Comparative Example 2 of the present invention 37.8 Zr 16.2 N 46 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0079] Fig.23 The Cr prepared in Comparative Example 4 of the present invention 39.6 Zr 19.4 N 41 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating.

[0080] In the XRD diffraction pattern, the horizontal axis is 2θ, the unit is °, and the vertical axis is the X-ray diffraction intensity (intensity), the unit is au; according to the selected area electron diffraction pattern (SAED) of the alloy coating, the corresponding radial intensity profile is obtained, which is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal axis, the unit is angstrom The vertical axis is the electron diffraction intensity (intensity), and the unit is au.

[0081] In the XRD diffraction pattern and the radial intensity profile corresponding to the SAED pattern, au has a well-known meaning in the art.

[0082] In some SEM images, when preparing the cross-section samples to be tested, some cross-section delamination occurs when the silicon wafer is brittle, but it does not affect the observation and analysis of the cross-section morphology. The positions of different structural layers in the substrate and protective coating can be determined according to the thickness of the corresponding structural layers. Fig.13 and Fig.14 The structural layer position mark in .

[0083] Description of reference numerals: 1 is a vacuum chamber, 2 is a sample stage, 3 is a DC anode, 4 is a chromium target (also denoted as a Cr target), and 5 is a zirconium target (also denoted as a Zr target); wherein, the Cr target 4 is a Cr target with radio frequency assisted DC cathode power generation, and the Zr target 5 is a Zr target with radio frequency assisted DC cathode power generation;

[0084] 100 is a substrate, 200 is a transition layer (also called a transition film layer), 300 is the alloy coating of the present application, and 400 is a surface layer (also called a surface film layer). DETAILED DESCRIPTION

[0085] The present invention will be further described in detail below in conjunction with the accompanying drawings, embodiments and examples. It should be understood that these embodiments and examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive. It should also be understood that the present invention can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. For example, the features described or described as part of an embodiment can be combined in another embodiment in a suitable manner to produce a new embodiment. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present invention. It should be understood that the present invention can be implemented without one or more of these details.

[0086] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing implementation modes and embodiments and are not intended to limit the present invention.

[0087] the term

[0088] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0089] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, which include any combination of any two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions: A, B, and "a combination of A and B".

[0090] In the present invention, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0091] In the present invention, unless otherwise specified, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other expressions that mean "one or more" are also understood in the same way unless otherwise specified.

[0092] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.

[0093] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of the present invention, solve the technical problem of the present invention, and achieve the expected technical effect of the present invention.

[0094] Herein, "preferred", "better", "more preferred" and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0095] In the present invention, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent different technical solutions are related in terms of the contents covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of the present invention. In the present invention, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0096] In the present invention, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist.

[0097] In the present invention, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0098] As used herein, the terms "comprising", "including" and "comprising" are synonymous and are inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps.

[0099] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0100] In the present invention, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0101] In this article, unless otherwise specified, "about" means within a certain range above or below the number, and the fluctuation range may vary depending on the type and value of the number. For example, it is allowed to be within a range of ±10%, ±5%, ±2%, ±1%, ±0.5%, etc. For example, about 2° can be selected from 2°±0.02°, etc.

[0102] The temperature parameters in the present invention, if not specifically limited, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0103] In the present invention, the term "room temperature" generally refers to 4°C to 35°C, such as 20°C ± 5°C. In some embodiments of the present invention, "room temperature" refers to 10°C to 30°C. In some embodiments of the present invention, "room temperature" refers to 20°C to 30°C.

[0104] In the present invention, the term "normal temperature" generally refers to 20°C to 35°C, for example, 20°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C.

[0105] In the present invention, when it comes to the unit of the data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3-5h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).

[0106] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as a reference separately. Unless they conflict with the invention purpose and / or technical solution of the present application, the cited documents involved in the present invention are cited with all contents and all purposes. When the present invention involves cited documents, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the present invention involves cited documents, the examples and preferred embodiments of the cited relevant technical features may also be incorporated into this application as references, but are limited to the ability to implement the present invention. It should be understood that when the content of the citation conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0107] The mass or weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the proportional relationship of the mass or weight between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass or weight described in the description of the embodiments of the present invention may be units known in the chemical industry such as μg, mg, g, and kg.

[0108] In the present invention, if there are multiple steps involved in the method flow, unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0109] When describing positional relationships, unless otherwise specified, when an element such as a layer, film or substrate is referred to as being "on" another film layer, it can be directly on the other film layer or there can be an intermediate film layer. Further, when a "layer" is referred to as being "under" another layer, it can be directly below or there can be one or more intermediate layers. It is also understood that when a "layer" is referred to as being "between" two layers, it can be the only layer between the two layers, or there can be one or more intermediate layers.

[0110] Where “including,” “having,” and “comprising” are used herein, it is intended to cover a non-exclusive inclusion, and another component may also be added unless explicit limiting terms such as “only,” “consisting of,” etc. are used.

[0111] Unless mentioned to the contrary, terms in the singular may include plural forms and should not be construed as being one in number.

[0112] The inventors of the present application have found through extensive research and experimental analysis that conventional Cr-Zr-N alloy coatings generally have a columnar crystal structure (columnar crystals are formed in more than 90% of cases), and that a high content of columnar crystals will promote the formation of a highly ordered structure arranged in a directional manner. In the highly ordered structure, there are a large number of inter-crystal gap defects caused by crystallization, which are mainly manifested as penetrating column gaps. There are shadows between the columnar crystals in the corresponding scanning electron microscope (SEM) cross-sectional view. These penetrating column gaps may be one of the important factors leading to poor corrosion resistance of the alloy coating. The inventors of the present application speculate that the conventional directional ordered structure easily leads to an insufficiently dense coating. Under corrosive conditions, the corrosive medium can quickly penetrate the coating through the gaps and react with the substrate, thereby leading to poor corrosion resistance of the alloy coating.

[0113] In addition, the alloy materials on the market are currently mainly protected by means of anodic oxidation, magnetron sputtering, etc. For example, aluminum alloys are mainly protected by anodic oxidation, and its working principle is: the aluminum alloy material is placed in a strong acid or strong alkali solution to form oxides and metal and alloy coatings on the surface to form surface protection; because the solution is a strong acid or strong alkali, the product formed by this method is not glossy enough and has a low hardness. In addition, a large amount of wastewater, waste liquid and waste gas are generated during the production process, which is not good for the environment.

[0114] Based on this, in a first aspect of the present invention, an alloy coating is provided, which contains a Cr-Zr-N alloy material, and the X-ray diffraction pattern of the alloy coating has at least one 2θ(°) diffraction peak with a half-height width ≥ 2° in the range of 30° to 50°, and in a radial intensity profile corresponding to a selected area electron diffraction pattern (SAED) of the alloy coating, it is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the abscissa and the diffraction intensity as the ordinate, The range has at least The alloy coating has excellent corrosion resistance and high hardness, and can be used as at least a part of the protective coating of the plated product.

[0115] The alloy coating provided in the present application contains Cr, Zr and N elements, and is also referred to as a Cr-Zr-N alloy coating.

[0116] The alloy coating provided by the present invention has excellent corrosion resistance. For example, the alloy coating provided by the present invention is prepared on the surface of an aluminum alloy. When the salt spray corrosion resistance test is conducted using the ASTM B117 salt spray test method, the alloy coating can pass the 24h test, and most embodiments can pass the 48h test, while the traditional alloy coating generally has difficulty passing the 8h test. In addition, the high hardness characteristics of the alloy coating provided by the present invention can reduce or weaken scratch damage.

[0117] In the Cr-Zr-N alloy coating of the present invention, Cr and Zr can form a bond energy of a certain strength, which can promote the rapid growth of the Cr-Zr alloy during the deposition process. The addition of nitrogen can promote the re-nucleation of the Cr-Zr alloy to form the Cr-Zr-N alloy of the present invention. By improving the density of the coating nucleation, the corrosion resistance and hardness can be improved.

[0118] In some embodiments, an alloy coating is provided, which contains a Cr-Zr-N alloy material, and the alloy coating satisfies the following two characteristics:

[0119] The X-ray diffraction pattern of the alloy coating has a peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak within the range of 30° to 50° satisfies ≥ 2°;

[0120] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating, the characteristic atomic distance is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of At least one within the range

[0121] The alloy coating provided by the present invention may also be recorded as "the alloy coating of the present application", "the alloy coating provided by the present application", "the alloy coating described in the present application", "the alloy coating of the present invention", "the alloy coating of the present invention", "the Cr-Zr-N alloy coating of the present invention" or "the alloy coating described in the present invention", and includes but is not limited to the alloy coating provided in the first aspect. The alloy coating contains a Cr-Zr-N alloy material, and the atomic ratio of the Cr element, the Zr element and the N element in the Cr-Zr-N alloy material is recorded as x:y:z, wherein x, y and z are atomic ratios and are each independently a positive number. It can be understood that the components in the alloy coating may not be limited to the three elements of Cr, Zr and N. The alloy coating provided by the present invention may also be referred to as a Cr-Zr-N alloy coating or a CrZrN alloy coating. In the present invention, the form of the Cr-Zr-N alloy material is not particularly limited, and may be, but is not limited to, the form of an alloy coating.

[0122] The means for structural characterization of the Cr-Zr-N alloy coating in the present invention can also be used to characterize the Cr-Zr-N alloy material provided by the present invention, and the Cr-Zr-N alloy material may not be limited to the coating form, but may be an independent raw material, such as an alloy sheet, an alloy plate, etc.

[0123] In the present invention, unless otherwise specified, the "atomic ratio" of two or more elements means the atomic number ratio.

[0124] In the present invention, unless otherwise specified, "Cr-Zr-N alloy" and "CrZrN alloy" both refer to alloys containing Cr, Zr and N elements, and other alloying elements may be contained, and the two can be used interchangeably.

[0125] In the present invention, unless otherwise specified, "Cr-Zr-N ternary alloy" and "CrZrN ternary alloy" both refer to an alloy composed of three elements: Cr element, Zr element and N element.

[0126] Different from the conventional Cr-Zr-N alloy coatings which are nanocrystalline and have a high columnar crystal content (which have a large number of through-type pores), the Cr-Zr-N alloy coating provided by the present invention can form a dense coating with a "highly disordered and fully densely packed" characteristic structure, containing very few through-type pores or no through-type pores. In the alloy coating of the present invention, the three atoms of Cr, Zr, and N with different radii condense into a highly disordered state during the deposition process and form a tight stack, which makes the alloy coating easy to grow densely and can inhibit the formation of continuous and large number of through-type gaps, thereby forming an effective isolation between the substrate and the corrosive environment. In addition, since the alloy coating provided by the present invention contains chromium and zirconium elements, the coating has sufficient self-chemical inertness in a corrosive environment. The Cr-Zr-N alloy material in the alloy coating of the present invention not only has a highly disordered atomic distribution, but also has sufficient dense stacking at the atomic scale, thereby avoiding or reducing the penetrating gaps caused by highly ordered arrangement. The dual characteristics of "highly disordered distribution" and "sufficiently dense stacking" of atoms in the alloy coating make the alloy coating have a highly dense structure, which can provide excellent corrosion resistance and high hardness characteristics. In short, the alloy coating provided by the present invention effectively reduces the common defects of traditional alloy coatings. For example, the penetrating gaps between grains in the columnar crystal structure coating are greatly reduced or disappear, making the alloy coating more conducive to dense growth and obtaining a smooth surface, thereby giving the alloy coating excellent corrosion resistance and high hardness characteristics.

[0127] Corrosion-resistant coatings must be inherently inert and fully isolated. "Inherently inert" means that the coating material is sufficiently inert and not prone to chemical reactions with the corrosive media in the service environment. "Full isolation" means that the coating structure is dense enough to fully isolate the substrate from the service environment, preventing or delaying the reaction between the substrate and the corrosive media therein, thereby achieving the purpose of corrosion resistance.

[0128] In the present invention, whether the constituent atoms of the coating have a "highly disordered" state is evaluated by XRD technology. Specifically, the XRD diagram of the Cr-Zr-N alloy coating shows wide and gentle ridges, and these "wide and gentle ridges" are called "broad peaks" of the 2θ (°) diffraction peak. The length of the orderly arrangement of atoms can be obtained by using the Scherrer formula from the half-height width of the broad peak. The calculation method is: D = Kλ / (β·cosθ), where D is the length of the orderly arrangement of atoms (representing the grain size in crystalline materials), K is the Scherrer constant, λ is the wavelength of X-rays; β is the half-height width of the diffraction peak (referring to the width value at half the height of the diffraction peak, Full Width at Half Maximum, FWHM), and θ is the diffraction angle. It can be seen that the half-height width FWHM is inversely proportional to the length D of the orderly arrangement of atoms, and the shorter the length D of the orderly arrangement of atoms, the higher the disorder of the atomic distribution. Therefore, the half-width (FWHM) of the diffraction peak within a specific range in the XRD diagram can be used to reflect the degree of disordered distribution of atoms: the wider the half-width (FWHM), the shorter the length of the ordered arrangement of atoms, and the more disordered the overall atomic distribution; the aforementioned wide and gently raised "broad peak" can reflect the highly disordered distribution of atoms in the material as a whole.

[0129] Generally speaking, the higher the atomic order, the stronger the crystallinity, the easier it is to form large-sized grains over a long distance, the narrower the diffraction peak in the XRD diagram, and high crystallinity is often accompanied by sharp peaks. In the alloy coating of the present invention, the three atoms of Cr, Zr, and N can be highly disordered in the Cr-Zr-N alloy coating as a whole, so that it appears as a wide and gentle ridge (broad peak) in the XRD diagram of the Cr-Zr-N alloy coating, which is manifested as "at least one peak in the diffraction angle 2θ (°) range of 30° to 50° is a "broad peak".

[0130] In the present invention, unless otherwise specified, the "broad peak" in the XRD pattern can be defined as a half-height width satisfying ≥2°. The half-height width of the broad peak can further be ≥2.19°, further ≥2.2°, further ≥2.3°, further ≥3°, further ≥3.5°, further ≥4°, further ≥5°. The half-height width of any "broad peak" in the XRD diagram can independently be any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values ​​(except 10°) and less than or equal to 10°, and can also be selected from the interval consisting of any two of the following values: 2°, 2.19°, 2.2°, 2.23°, 2.25°, 2.5°, 3°, 3.5°, 3.52°, 3.92°, 4°, 4.04°, 4.42°, 4.5°, 5°, 5.5°, 5.54°, 5.56°, 6°, 6.05°, 6.5°, 7°, 7.5°, 8.42°, 8.5°, 8.85°, 9°, 9.11°, 9.2°, 9.25°, 9.33°, 9.35°, 9.4°, 9.5°, 10°, etc. As non-limiting examples, any of the following ranges may be selected: 2° to 10°, 2° to 9.5°, 2° to 9.4°, 2.1° to 9.5°, 2.1° to 9.4°, 2.15° to 9.35°, 2.19° to 9.33°, etc.

[0131] In the present invention, unless otherwise specified, a "sharp peak" in an X-ray diffraction (XRD) pattern refers to a diffraction peak with a half-height width < 2°.

[0132] In more detail, in the alloy coating provided by the present application, the XRD pattern has peaks within the diffraction angle 2θ(°) range of 30° to 50°, and at least one of the diffraction peaks in the XRD spectrum is a broad peak. The special microstructural state in which at least one peak is a "broad peak" can be represented by "having at least one 2θ(°) diffraction peak with a half-width ≥2° within the range of 30° to 50°" or "having at least one 2θ(°) diffraction peak with a half-width ≥2° within the range of 30° to 50°". The following method can be used to determine whether "having at least one 2θ(°) diffraction peak with a half-width ≥2° within the range of 30° to 50°" is satisfied: in the XRD spectrum, if the half-width value of the 2θ(°) diffraction peak is ≥2°, it is judged as a "broad peak"; if the half-width value of the 2θ(°) diffraction peak is <2°, it is judged as a sharp peak. For a certain specified 2θ(°) position, it can be any of the three states of no peak, broad peak or sharp peak. In the X-ray diffraction (XRD) diagram, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious.

[0133] In traditional alloy coatings with a high content of columnar crystals (including traditional Cr-Zr-N alloy coatings), the diffraction peaks in the diffraction angle 2θ (°) range of 30° to 50° often appear as sharp peaks with a half-height width < 2°, and no broad peaks appear.

[0134] In the present invention, conventional instruments and methods in the art can be used to obtain the XRD pattern of the alloy coating, for example, a German Bruker D8 Advance XRD diffractometer can be used.

[0135] In some embodiments, the X-ray diffraction pattern of the alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and at least one 2θ(°) diffraction peak in the range of 30° to 50° is a broad peak, and the half-width value of the broad peak can be referred to the examples in the context; taking the half-width of the broad peak ≥2.19° as an example, at least one 2θ(°) diffraction peak in the range of 30° to 50° satisfies ≥2.19°.

[0136] In some embodiments, the X-ray diffraction pattern of the alloy coating of the present invention has a broad peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of the broad peak can be referred to the examples in the context.

[0137] In some embodiments, the X-ray diffraction pattern of the alloy coating of the present invention has two or more broad peaks within a diffraction angle 2θ (°) range of 30° to 50°, and the half-height widths of these broad peaks can be independently referred to in the examples in the context.

[0138] In some embodiments, in the X-ray diffraction pattern of the alloy coating of the present invention, all 2θ(°) diffraction peaks within the diffraction angle 2θ(°) range of 30° to 50° are broad peaks, that is, there are no sharp peaks, and the half-height widths of these broad peaks can be independently referred to the examples in the context.

[0139] In some embodiments, the X-ray diffraction pattern of the alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and the half-width of the 2θ(°) diffraction peak in the range of 30° to 50° each independently satisfies ≥2°, further can each independently satisfy ≥2.19°, further can each independently satisfy ≥2.2°, further can each independently satisfy ≥2.3°, further can each independently satisfy ≥3°, further can each independently satisfy ≥3.5°, further can each independently satisfy ≥4°, further can each independently satisfy ≥5°.

[0140] In some embodiments, the X-ray diffraction pattern of the alloy coating is obtained by Cu target Kα radiation.

[0141] In the present invention, the following instruments and methods can be used to obtain the XRD pattern of the alloy coating: using a German BrukerD8 Advance XRD diffractometer, in θ-2θ mode, using Cu target Kα rays, a wavelength λ of 0.15406nm, the X-ray tube is controlled at 40kV and 40mA, the scanning range is 20° to 80°, and precise scanning measurement is performed with a step size of 0.01°.

[0142] The half-width value can be obtained by conventional analysis methods in the art (including but not limited to analysis software provided by the instrument supplier). For example, the step of obtaining the half-width value may include: firstly performing correction processing on the diffraction peak, which may include: smoothing, subtracting the background, removing the Kα2 line, subtracting the instrument broadening, etc., and fitting the diffraction peak with the Pseudo-Voigt function to obtain the half-width value of the diffraction peak.

[0143] The analysis software is not particularly limited. Without limitation, EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and microanalysis, The university of Sydney) can be used to process the spectrum data. For example, the following method can be used: first, a scale calibration is performed, and then the center of the diffraction ring transmission spot is determined, and then converted into an XRD spectrum (wherein the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak is deducted from the straight line background, and then fitted with a Voigt function to obtain the half-height width of the corresponding diffraction peak.

[0144] Regarding the characterization of the degree of atomic density in alloy coatings, traditional XRD patterns cannot be used to characterize it well. This is because: when detecting physical vapor deposition (PVD) films or coatings at the atomic scale (such as diameter <3nm), the XRD method often has insufficient resolution due to the large wavelength of X-rays (>0.1nm), and is not suitable for PVD films or coatings with low order (such as grains or amorphous grains with a diameter <3nm).

[0145] In the present invention, whether the atoms constituting the coating have reached "sufficiently densely packed" is evaluated by the selected area electron diffraction pattern (Selected Area Electron Diffraction, SAED). The electron wave is selected because its wavelength is significantly smaller (<0.01nm), so the resolution is higher. Specifically, if there are only continuous diffraction rings with consistent brightness on the SEAD graph, and the diffraction rings are relatively wide, it indicates that the atoms in the coating are densely packed in a highly random mixed manner. In order to quantitatively characterize, the SAED spectrum can be converted into a characteristic atomic spacing (d)-radial intensity profile, in which the characteristic atomic spacing (d) is the horizontal coordinate and the diffraction intensity is the vertical coordinate. If the diffraction rings in the SEAD are relatively wide, then correspondingly, the half-height width of the radial intensity profile is relatively wide, reflecting that the atomic arrangement in the alloy coating is densely packed.

[0146] In this application, in terms of atomic size, the Cr atomic radius is The atomic radius of Zr is The atomic radius of N is The three atoms with different diameters have a suitable atomic size mismatch, and under the condition of high random mixing, a fully dense structure can be formed. In the growth process of PVD film or alloy coating, the fully dense stacking of atoms in Cr-Zr-N alloy coating makes the alloy coating easy to grow densely, which can inhibit the formation and growth of columnar crystals originally caused by local ordering, and then make it difficult for continuous through-type pores to form in large quantities. Thus, the half-height width of the radial intensity profile can be used as the characteristic parameter of the fully dense structure of the alloy coating to reflect the dense packing of atoms in the alloy coating. The larger the value of the half-height width, the better the dense packing of atoms in the alloy coating. In short, the present invention adopts the half-height width of the radial intensity profile of SAED as the characteristic parameter of fully dense atomic stacking, which is in line with scientific principles and has scientificity.

[0147] When the half-height width of the radial intensity profile is greater than a certain threshold, the atoms in the coating can be fully densely packed. According to a large number of experimental explorations by the inventors, in the present invention, unless otherwise specified, the half-height width threshold for judging whether the atoms are fully densely packed in the SAED-radial intensity profile is determined as That is to say When the atoms are fully packed together,

[0148] In the present invention, a transmission electron microscope (TEM) technique may be used to obtain a radial intensity profile of a characteristic atomic spacing (d) of an alloy coating sample.

[0149] In the present invention, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating can be recorded as a SAED-radial intensity profile, and can also be recorded as a characteristic atomic spacing-intensity quantitative spectrum of the selected area electron diffraction pattern (SAED pattern). The selected area electron diffraction pattern obtained by transmission electron microscopy can be recorded as a TEM selected area electron diffraction pattern, and can also be recorded as a TEM-SAED pattern. The SAED-radial intensity profile obtained by transmission electron microscopy can also be recorded as a TEM-SAED-radial intensity profile.

[0150] In the present invention, the alloy coating (including the Cr-Zr-N alloy coating of the present invention) can be obtained by using conventional instruments and methods in the art, and the corresponding radial intensity profile can be obtained according to the selected area electron diffraction pattern (SAED) of the alloy coating. It is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal coordinate and the unit being angstroms. The vertical axis represents the electron diffraction intensity.

[0151] In the present invention, unless otherwise specified, the radial intensity profile of the SAED pattern is It is judged as a broad peak; For a specific characteristic atomic spacing, it can be any of the three states of no peak, sharp peak or broad peak. In the radial intensity profile, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious. Unless otherwise specified, the "broad peak" in the radial intensity profile of the selected area electron diffraction pattern (SAED pattern) refers to The diffraction peak of diffraction peaks.

[0152] In the present invention, the radial intensity profile or SAED-radial intensity profile, unless otherwise specified, can be obtained using TEM technology.

[0153] In the present invention, unless otherwise specified, the “broad peak” in the radial intensity profile corresponding to the SAED pattern can be defined as Broad peak

[0154] In the present invention, the following transmission electron microscopy (TEM) method can be used (but not limited to) to obtain the half-width at half maximum data in the radial intensity profile corresponding to the selected area electron diffraction pattern:

[0155] TEM test sample preparation: The Helios 5 CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.

[0156] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) of Thermo Fisher Co., Ltd. of the United States was used with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain the selected area electron diffraction pattern (SAED) of the sample. Based on the selected area electron diffraction pattern (SAED) image, a radial intensity profile was obtained, and the half-height width value of the diffraction peak was obtained by using the integrated half-height width assignment.

[0157] According to the principle that the half-width of the diffraction peak in the radial intensity profile corresponds to the width of the diffraction ring in the selected area electron diffraction pattern (SAED) pattern, the selected area electron diffraction pattern (SAED) pattern of the alloy coating can be converted into the corresponding radial intensity profile.

[0158] Those skilled in the art know that the larger the width of the diffraction ring in the selected area electron diffraction pattern, the stronger the random mixing degree of the atoms, and the more densely packed the atoms are in the alloy coating of the present invention; the half-width of the diffraction peak in the radial intensity profile is a quantitative indicator of the diffraction ring width, and the larger the half-width value, the more densely packed the atoms are.

[0159] In some embodiments, the selected area electron diffraction pattern (SAED) of the alloy coating of the present invention is obtained using a transmission electron microscope (TEM) characterization technique, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

[0160] In some embodiments, in the radial intensity profile of the selected area electron diffraction pattern of the alloy coating of the present invention, The range has at least diffraction peaks.

[0161] In the radial strength cross-sectional diagram of the alloy coating provided by the present invention, The half-height width of the diffraction peak in the range has an upper limit due to the atomic close packing limit. Non-limiting examples of the upper limit are as follows:

[0162] In the present invention, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be independently any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values ​​and less than or equal to the aforementioned upper limit value (such as ), and can also be independently selected from an interval consisting of any two of the following values: As a non-limiting example, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be selected from any of the following ranges: wait.

[0163] In some embodiments, in the radial strength profile of the alloy coating of the present invention, In range

[0164] In some embodiments, in the radial strength profile of the alloy coating of the present invention, The half-height width of the diffraction peak within the range can be independently any of the following values, and can also be independently selected from the interval consisting of any two of the following values: As non-limiting examples, they can be independently selected from any of the following ranges: wait.

[0165] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating of the present invention is There is one broad peak in the range, and its half-height width can be found in the examples in the context.

[0166] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating of the present invention is There are 2 or more broad peaks in the range, and their half-height widths can be independently determined by referring to the examples in the context.

[0167] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating of the present invention is All diffraction peaks in the range are broad peaks. See also context definition.

[0168] In some embodiments, the characteristic atomic spacing of the alloy coating of the present invention is obtained using TEM diffraction data; wherein, the TEM diffraction test of the alloy coating is performed using an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

[0169] In some embodiments, the TEM test uses a mode with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain a selected area electron diffraction pattern (SAED) of the alloy coating.

[0170] The alloy coating in the present application is not clearly divided into the traditional perfect single crystal or fully amorphous state, but focuses on the degree of dense packing of atomic arrangement, which is closely related to the disorder of atomic arrangement and the mismatch of atomic size; the highly dense alloy coating provided by the present invention has excellent corrosion resistance and high hardness properties in terms of performance, and structurally satisfies the requirements of having at least one broad peak (furthermore, there may be no sharp peak, that is, all are broad peaks) in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diagram and the radial intensity profile of the selected area electron diffraction pattern is There is at least one broad peak in the range (furthermore, there may be no sharp peaks, that is, all are broad peaks).

[0171] The alloy coating provided by the present invention may or may not contain doping elements, and can be flexibly selected according to the additional functional requirements of the alloy coating. It is understood that in the present invention, when doping elements are contained, the type and amount of doping elements are limited to being able to form the alloy coating structure of the present invention without affecting the realization of excellent corrosion resistance and high hardness.

[0172] In the present invention, the chemical formula of the Cr-Zr-N alloy material in the alloy coating of the present invention can be recorded as (Cr x Zr y N z )M a , where x, y and z are independently atomic ratios and are all positive numbers, M is a doping element, and a is the atomic ratio of the M element and is 0 or a positive number. During the nucleation process, N atoms can penetrate into the pores of large-sized Cr and Zr metal grains to achieve a better pore filling effect, making the coating atoms more densely stacked, and can also inhibit the growth defects of the thin film columnar crystal structure and improve the corrosion resistance of the coating.

[0173] Unless otherwise specified, the Cr-Zr-N alloy material in the alloy coating of the present invention mainly comprises three elements: Cr, Zr and N. Further, the sum of the atomic ratios of the three elements accounts for ≥95% of the sum of the atomic ratios of all elements in the Cr-Zr-N alloy material (corresponding to 0≤a / (x+y+z+a)≤0.05, for example, 0≤a / (x+y+z)≤0.05), further such as ≥98% (corresponding to 0≤a / (x+y+z+a)≤0.02, for example, 0≤a / (x+y+z)≤0.02), and further such as Cr-Zr-N ternary alloy material (at this time, a=0). By limiting the content of doping elements, the influence of doping elements on the highly disordered and fully densely packed atoms in the alloy nitrogen coating of the present application can be minimized, which is beneficial to reduce the elements required for doping or reduce the difficulty of doping, simplify the preparation process, promote the coordinated deposition of Cr, Zr and N to form a denser coating, and is beneficial to achieve better corrosion resistance and higher hardness.

[0174] In some embodiments, the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , wherein x, y, z and a are independently atomic ratios, 15≤x≤81.6, 12.1≤y≤78.8 and 4.7≤z≤35.9, M is a doping element, and 0≤a / (x+y+z+a)≤0.05 (optionally, 0≤a / (x+y+z)≤0.05). At this time, the atomic ratios between Cr, Zr and N elements conform to a certain proportional relationship x:y:z. Traditional alloy coatings mostly adopt nitrogen-rich designs. In order to improve the hardness of the coating, the atomic percentage of nitrogen is usually higher than 40%. Moreover, this type of alloy coating is often designed with a certain Cr content to promote the formation of columnar crystals during the nucleation and crystallization growth of the film. When the Cr-Zr-N alloy material in the alloy coating has the above-mentioned element ratio, it is conducive to forming a denser structure and obtaining better corrosion resistance. At this time, during the nucleation process, N atoms can penetrate into the pores of large-sized Cr and Zr metal grains, better achieve the pore filling effect, make the coating atoms stack more densely, and better inhibit the growth defects of the columnar crystal structure of the film, thereby better improving the corrosion resistance of the coating.

[0175] When a is 0, the Cr-Zr-N alloy material does not contain doping elements, corresponding to the Cr-Zr-N ternary alloy material. When a>0, the Cr-Zr-N alloy material contains doping elements, wherein a / (x+y+z) is numerically equal to the relative atomic percentage of the doping element M relative to Cr, Zr, and N, and a / (x+y+z+a) is numerically equal to the atomic percentage of the doping element in the Cr-Zr-N alloy material.

[0176] In some embodiments, a / (x+y+z)=0. At this time, corresponding to the Cr-Zr-N ternary alloy material, the composition is simple, and it is easier to prepare and control. At this time, the Cr-Zr-N ternary alloy coating can obtain a dense structure, and can achieve excellent comprehensive properties of high corrosion resistance and high hardness.

[0177] In some embodiments, 0

[0178] ​In some embodiments, 0

[0179] In some preferred embodiments, 0

[0180] In some embodiments, the sum of x, y and z is 100. At this time, the ratio of the three atoms of Cr, Zr and N is constrained within a more appropriate range, and the prepared alloy coating is conducive to obtaining a denser structure, better corrosion resistance and higher hardness.

[0181] In some embodiments, when the proportions of 15≤x≤81.6, 12.1≤y≤78.8 and 4.7≤z≤35.9 are satisfied and x+y+z=100, x can be any of the following values ​​or an interval consisting of any two of the following values: 15.0, 29.7, 34.5, 41.3, 47.1, 52.0, 53.8, 54.8, 60.9, 61.4, 81.6, etc.

[0182] In some embodiments, when the proportions of 15≤x≤81.6, 12.1≤y≤78.8 and 4.7≤z≤35.9 are satisfied and x+y+z=100, y can be any of the following values ​​or an interval consisting of any two of the following values: 12.1, 13.0, 13.7, 17.4, 26.1, 30.0, 33.2, 35.1, 40.0, 49.5, 50.1, 78.8, etc.

[0183] ​​In some embodiments, when the proportions of 15≤x≤81.6, 12.1≤y≤78.8 and 4.7≤z≤35.9 are satisfied and x+y+z=100, z can be any of the following values ​​or an interval consisting of any two of the following values: 4.7, 5.4, 6.2, 10.1, 13.0, 20.2, 25.5, 35.5, 35.9, etc.

[0184] In some embodiments, the doping element is a non-metallic element, a metallic element, or a combination thereof, which can be flexibly selected according to the additional functional requirements of the Cr-Zr-N alloy coating.

[0185] Without limitation, the non-metallic element may include one or more of O, C, B, Si and Ar. Without limitation, the metal element may include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0186] In some embodiments, the elemental composition of the alloy coating provided by the present invention can be expressed as Cr-Zr-Qum-Qm-N, wherein Qum is a non-metallic element, which may include but is not limited to one or more of O, C, B, Si, Ar, etc., and Qm is a metal element, which may include but is not limited to one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al. In some embodiments, the atomic percentage of Qum is ≤5%. In some embodiments, the atomic percentage of Qum is 0. In some embodiments, the atomic percentage of Qum is 0.01% to 5%, or any of the following percentages, or less than or equal to any of the following percentages but greater than 0, or selected from the numerical interval consisting of any two of the following percentages: 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, etc. In some embodiments, the atomic percentage of Qm is ≤5%. In some embodiments, the atomic percentage of Qm is 0. In some embodiments, the atomic percentage of Qm is 0.01% to 5%, and can also be any of the following percentages, or less than or equal to any of the following percentages but greater than 0, or a numerical range consisting of any two of the following percentages: 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, etc.

[0187] In some embodiments, the elemental composition of the alloy coating provided by the present invention is Cr-Zr-Qum-N, where Qum is a non-metallic element, and may include but is not limited to one or more of O, C, B, Si, Ar, etc. Further, the atomic percentage of Qum may satisfy ≤5%. In some embodiments, the atomic percentage of Qum is 0. In some embodiments, the atomic percentage of Qum is 0.01% to 5%, and may also be any of the following percentages, or less than or equal to any of the following percentages but greater than 0, or selected from the numerical interval consisting of any two of the following percentages: 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, etc.

[0188] In some embodiments, the element composition of the alloy coating provided by the present invention is Cr-Zr-Qm-N, Qm is a metal element, which may include but is not limited to one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu, and Al. Further, the atomic percentage of Qm may satisfy ≤5%. In some embodiments, the atomic percentage of Qm is 0. In some embodiments, the atomic percentage of Qm is 0.01% to 5%, or any of the following percentages, or less than or equal to any of the following percentages but greater than 0, or a numerical interval consisting of any two of the following percentages: 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, etc.

[0189] In some embodiments, the percentage of the sum of the number of atoms of Cr, Zr and N elements relative to the sum of the number of atoms of all elements in the alloy coating is ≥95%, and may further satisfy ≥98%. In some embodiments, the percentage of the sum of the number of atoms of Cr, Zr and N elements relative to the sum of the number of atoms of all elements in the alloy coating is 95% to 100%, or may be any of the following percentages, or greater than or equal to any of the following percentages but less than or equal to 100%, or a numerical interval consisting of any two of the following percentages: 95%, 96%, 97%, 98%, 98.5%, 99%, 99.5%, 99.9%, 99.95%, 99.99%, 100%, etc., for example, it may be 98% to 100%.

[0190] It should be noted that in any embodiment of the present application, the alloy coating described in the present application is allowed to have inevitable impurities introduced during the preparation process. "Inevitable impurities" are not intentionally added impurities, and the main reason for their existence is that they are accidentally introduced during the preparation process; non-limiting examples of "inevitable impurities" include, for example, elements such as C and O present in the air, and may also come from components in raw materials or equipment. The atomic content of "inevitable impurities" in the alloy coating is usually trace or micro, which can generally be ignored, such as less than 0.01% atomic content. Taking the technical solution of "the alloy coating is a Cr-Zr-N ternary alloy material composed of Cr, Zr and N elements" as an example, at this time, theoretically, the alloy coating is composed of three elements: Cr, Zr and N, but trace or micro amounts of other elements other than Cr, Zr and N may be introduced during the preparation process, such as C, O, etc.

[0191] In some embodiments, based on any of the above suitable embodiments, the thickness of the alloy coating is d min ~6μm, where d min It can be selected from 10nm to 50nm, d min It can also be any of the following thicknesses, or be selected from the interval consisting of any two of the following thicknesses: 10nm, 20nm, 25nm, 30nm, 40nm, 50nm, etc. For example, the thickness of the alloy coating can be 25nm-6μm, 30nm-6μm, 40nm-6μm, 50nm-6μm, 1.0μm-2.5μm, 1.0μm-2.0μm, etc. By controlling the alloy coating to have a suitable thickness, the corrosion resistance and / or high hardness characteristics of the alloy coating can be more fully utilized. The thicker the alloy coating, the more conducive to improving the corrosion resistance and / or hardness of the alloy coating. Compared with traditional alloy coatings, the Cr-Zr-N alloy coating of the present invention can provide a denser structure, can achieve better high hardness characteristics and corrosion resistance under the same thickness, so that the coating thickness can be reduced on the basis of maintaining better coating protection characteristics, thereby helping to save raw materials, simplify the process, shorten the production cycle, and significantly reduce costs.

[0192] In some embodiments, the alloy coating has a thickness of 10 nm to 6 μm.

[0193] In some embodiments, the alloy coating has a thickness of 25 nm to 6 μm.

[0194] In some embodiments, the alloy coating has a thickness of 1 μm to 2.5 μm.

[0195] In the second aspect of the present invention, a film-coated product is provided, which includes a substrate and an alloy coating; wherein the alloy coating is located on at least one side of the substrate, and the alloy coating may be, but is not limited to, the alloy coating described in the first aspect of the present invention, or may be selected from an alloy coating prepared by the preparation method of the fourth aspect below. At this time, the alloy coating described in the present invention is present in the protective coating of the film-coated product, which gives the protective coating excellent corrosion resistance and high hardness.

[0196] The alloy coating provided by the present invention can be located on one side or both sides of the substrate.

[0197] In some embodiments, the surface material of the substrate is one of an alloy, a single metal and an inorganic non-metallic material. Without limitation, the material type of the alloy may include one or more of a nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based. Without limitation, the single metal may be any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium. Without limitation, the inorganic non-metallic material may include one or more of ceramics and glass. Without limitation, the inorganic non-metallic material may include a silicon wafer.

[0198] The alloy coating provided by the present invention can be applied to a variety of substrates, the materials of which include but are not limited to alloys, elemental metals and other materials, and can also be used for other types of substrates such as inorganic non-metallic materials (such as silicon wafers, ceramics, glass).

[0199] In some embodiments, the surface material of the substrate is one of light alloys or one of stainless steel alloys; optionally, the light alloy includes one or more of titanium alloy, aluminum alloy and magnesium alloy.

[0200] In some embodiments, the surface material of the substrate is one of light alloys; further, the light alloy may include one or more of titanium alloy, aluminum alloy and magnesium alloy.

[0201] In some embodiments, the surface material of the substrate is one of stainless steel alloys. Further, the stainless steel alloy can be any one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, etc.

[0202] In some embodiments, the coated article satisfies one or more of the following features:

[0203] The alloy coating is in direct contact with the substrate (in this case, there is no transition layer) or a transition layer is provided. Furthermore, the transition layer may be a single-layer structure or a multi-layer structure (that is, one or more structural layers may be formed between the Cr-Zr-N alloy coating provided by the present invention and the substrate);

[0204] The alloy coating is located on the surface of the coated product or a surface layer is provided on the side of the alloy coating away from the substrate; further, the surface layer can be a single-layer structure or a multi-layer structure (that is, one or more structural layers can continue to be formed on the Cr-Zr-N alloy coating provided by the present invention).

[0205] In this application, unless otherwise specified, "transition layer" and "transition film layer" have the same meaning and can be used interchangeably. Both refer to a structural layer with transitional properties located between the substrate and the alloy coating described in this application in a coated product, which can be a single-layer structure or a multi-layer structure.

[0206] In this application, unless otherwise specified, "surface layer" and "surface film layer" have the same meaning and can be used interchangeably. They both refer to the structural layer of the alloy coating described in this application in the coated product that is away from the substrate side and located on the surface of the product. It can be a single-layer structure or a multi-layer structure.

[0207] In some implementations, the alloy coating 300 of the present application is in direct contact with the substrate 100 (in this case, there is no transition layer).

[0208] In some embodiments, a transition layer 200 is provided between the alloy coating 300 and the substrate 100 of the present application.

[0209] In some implementations, the alloy coating 300 of the present application is located on the surface of the coated product.

[0210] In some embodiments, a surface layer 400 is further provided on a side of the alloy coating 300 of the present application away from the substrate 100 .

[0211] Figure 2 Schematic diagrams of the structures of the coated products in several embodiments of the present invention are provided: (A) includes a substrate 100 and the alloy coating 300 of the present application; (B) includes a substrate 100, a transition layer 200 and the alloy coating 300 of the present application; (C) includes a substrate 100, a transition layer 200, the alloy coating 300 of the present application and a surface layer 400; (D) includes a substrate 100, the alloy coating 300 of the present application and a surface layer 400.

[0212] When the alloy coating of the present application appears in the protective coating of the plated product, the position of the alloy coating can be flexibly set. For example, the alloy coating can be used for surface protection, in which case the alloy coating is located on the surface of the plated product; the alloy coating can also be used as an intermediate protective layer, in which case other structural layers are provided on the outside of the alloy coating, that is, the alloy coating can be used as a surface layer. Different coating position settings can achieve better scratch resistance and better corrosion resistance.

[0213] When the alloy coating of the present application is located on the surface of the coated product, a surface with a certain brightness can be provided for the coated product. When testing the chromaticity value of the alloy coating, the sample to be tested adopts a substrate material suitable for practical application, and detects the degree of improvement of the compactness and other properties of the substrate by the alloy coating. The L value, a value and b value of the sample can be tested by a CM-3700A-U desktop spectrophotometer produced by Konica Japan. The light receiving system selects the F2 light source, and the average value is taken after testing 6 matrix points for each sample. Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values. The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: the spectrophotometer is incident light on the surface of the sample to be tested, forming a reflection, and a reflectivity curve can be obtained. The amplitude of the curve can reflect the density of the material, which can be specifically characterized by the L value. On the basis of the same material, the higher its density, the larger the L value it displays.

[0214] In some embodiments, the coated product is one of a 3C digital product, an automotive product, an aerospace product, a wearable product, and a sports product.

[0215] Without limitation, 3C digital products may include but are not limited to mobile device components, wearable components, vehicle-mounted components, etc.

[0216] According to the difference in the main components of the substrate, the coated product can be any one of a light alloy product, a stainless steel product, a single metal, an inorganic non-metal-based product (such as a ceramic-based product, a silicon-based product, a glass-based product), etc., indicating that the main components of the substrate are light alloy, stainless steel, single metal, etc., respectively. Without limitation, light alloy products may include but are not limited to aluminum alloy products, titanium alloy products, magnesium alloy products, etc. Without limitation, stainless steel products may include but are not limited to austenitic stainless steel, ferritic stainless steel, martensitic stainless steel. Without limitation, single metal products may include but are not limited to zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium, further such as copper, aluminum, iron, silver and chromium.

[0217] In one embodiment, the coated product is an aluminum alloy product.

[0218] In one embodiment, the coated product is a stainless steel product.

[0219] In one embodiment, the coated product is an inorganic non-metal-based product, and may further be a silicon-based product, a ceramic-based product or a glass-based product.

[0220] In one embodiment, the coated product is a copper product.

[0221] In a third aspect of the present invention, an alloy coating composition is provided, wherein the alloy coating composition contains a Cr—Zr—N alloy material, and the Cr—Zr—N alloy material is as defined in the first aspect of the present invention.

[0222] The present invention may also provide a Cr-Zr-N alloy material as defined in the first aspect of the present invention, or may be a Cr-Zr-N alloy material in any embodiment in the context. The Cr-Zr-N alloy material has a suitable atomic size mismatch and a special atomic ratio, and can form the Cr-Zr-N alloy coating of the present invention with a high random mixing degree of "highly disordered and fully densely packed".

[0223] As an example, in some embodiments, the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , wherein x, y, z and a are each independently an atomic ratio, 15≤x≤81.6, 12.1≤y≤78.8 and 4.7≤z≤35.9, M is a doping element, and 0≤a / (x+y+z+a)≤0.05 (optionally, 0≤a / (x+y+z)≤0.05). Wherein, x, y, z and a / (x+y+z), a / (x+y+z+a) can be as defined in the first aspect. In some embodiments, 15≤x≤81.6, 12.1≤y≤78.8 and 4.7≤z≤35.9, and the sum of x, y and z is 100. In some embodiments, 0≤a / (x+y+z)≤0.02. In some embodiments, 0≤a / (x+y+z+a)≤0.02.

[0224] In some embodiments, the doping element is a non-metallic element, a metallic element, or a combination thereof. The non-metallic element may include, but is not limited to, one or more of O, C, B, Si, and Ar.

[0225] The metal element may include, but is not limited to, one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0226] In some embodiments, the Cr-Zr-N alloy material satisfies the following two characteristics:

[0227] The X-ray diffraction pattern of the Cr-Zr-N alloy material has a peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak within the range of 30° to 50° satisfies ≥ 2°;

[0228] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of At least one within the range

[0229] Furthermore, the XRD test results of the Cr-Zr-N alloy material and the radial intensity profile results corresponding to the selected area electron diffraction pattern can also refer to the description of the radial intensity profile corresponding to the X-ray diffraction pattern and the selected area electron diffraction pattern in the Cr-Zr-N alloy coating in this article, and the corresponding optional and preferred methods can also be applied to the Cr-Zr-N alloy material.

[0230] In the fourth aspect of the present invention, there is provided the use of the alloy coating described in the first aspect of the present invention as at least a part of the protective coating of a coated product, or the use of the alloy composition described in the third aspect of the present invention in preparing at least a part of the protective coating of a coated product.

[0231] In some embodiments, the protective coating of the coated article is a corrosion-resistant protective coating.

[0232] The alloy coating provided by the present invention can be used as at least a part of the protective coating in the plated product, can be used as a protective coating of a single structure layer, and can also be used as a layer in a multi-layer structure protective coating.

[0233] In the present invention, unless otherwise specified, "protective coating" refers to a coating located on the surface of a substrate, which may be the alloy coating of the present application, or other structural layers may be provided on the basis of the alloy coating of the present application, such as the aforementioned transition layer and / or surface layer. The position of the alloy coating of the present application in the protective coating of the plated product may be flexibly set, and reference may be made to the second aspect of the present invention.

[0234] The aforementioned coated products can be intermediate products or final products. Final products can be used or sold directly. Intermediate products can be further processed or assembled with other components into new products.

[0235] The alloy coating provided by the present invention can give the plated product excellent corrosion resistance. For example, when the alloy coating provided by the present invention is prepared on the surface of an aluminum alloy, the alloy coating of the present invention can pass the 24h test (the protection time is ≥ 24h in this case) when the salt spray corrosion resistance test is performed using the ASTM B117 salt spray test method. Most embodiments can also pass the 48h test (while traditional alloy coatings generally have difficulty passing the 8h test). In addition, the high hardness characteristics of the alloy coating provided by the present invention can reduce or weaken scratch damage.

[0236] The alloy coating provided by the present invention can have both excellent corrosion resistance and high hardness characteristics at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. When the alloy coating is relatively thin, the formed plated product can present a silvery white metallic color close to the metallic color of the substrate, which is more conducive to achieving a beautiful decorative effect without changing the color of the substrate.

[0237] In the fifth aspect of the present invention, a method for preparing an alloy coating is provided, which can be used to prepare the alloy coating described in the first aspect of the present invention or the coated product described in the second aspect. The method for preparing the alloy coating provided by the present invention is simple, easy to operate, green and environmentally friendly, and has the advantages of being quantifiable, highly efficient, and having good repeatability, and is suitable for industrial applications.

[0238] In some embodiments, the method for preparing the alloy coating comprises the following steps: using a vapor deposition technique to deposit the constituent elements of the alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio to form the alloy coating according to the first aspect of the present invention. It is understood that the constituent elements of the alloy coating include at least Cr, Zr and N.

[0239] The definition of the substrate can be found in the second aspect of the present invention.

[0240] In some embodiments, the vapor deposition technique is a physical vapor deposition technique. Further, the physical vapor deposition technique can be implemented by one or more of the following methods: vacuum evaporation, sputtering, arc plasma plating, ion plating, and molecular beam epitaxy.

[0241] In one embodiment, the physical vapor deposition method is magnetron sputtering coating.

[0242] In some embodiments, sputtering coating (such as magnetron sputtering coating) technology is used to deposit the constituent elements of the alloy coating of the present invention on at least a portion of the surface of the substrate according to a preset atomic ratio.

[0243] In some embodiments, see Figure 1 The device shown. Figure 1 The device shown includes a vacuum chamber 1, a sample stage 2, a DC anode 3, a chromium target 4, and a zirconium target 5; wherein the chromium target 4 is a chromium target with radio frequency assisted DC cathode power supply, and the zirconium target 5 is a zirconium target with radio frequency assisted DC cathode power supply. The figure is not drawn in a 1:1 ratio, and the relative sizes of the components are drawn in the figure only as examples to facilitate understanding of the present invention, but are not necessarily drawn in true proportions. The proportions in the figure do not constitute a limitation of the present invention. By comparing the N-containing 2 Gas (such as Ar / N 2The alloy coating of the present invention can be formed by reactive sputtering of a mixed gas.

[0244] In some embodiments, a chromium-zirconium alloy target is used.

[0245] In some embodiments, the preparation method of the alloy coating, taking the sputtering coating method (such as magnetron sputtering coating) as an example, comprises the following steps: under the condition of introducing a mixed gas containing argon and a nitrogen-containing gas, using one or more targets including chromium and zirconium, sputtering and depositing the constituent elements of the alloy coating on at least a portion of the surface of the substrate to form the alloy coating. The nitrogen-containing gas can be but is not limited to nitrogen. At this time, the gas volume ratio of argon and nitrogen in the mixed gas can be (2-6):1, for example, 2:1, 3:1, 4:1, 5:1, 6:1, etc. When nitrogen is selected as the nitrogen-containing gas and the nitrogen content is controlled to a certain level, the performance of the alloy coating of the present invention can be further adjusted.

[0246] The target material may include one or more of a chromium target, a zirconium target and an alloy target. The alloy target includes at least two metal elements in the alloy coating. In some preferred examples, the atomic ratio of the metal elements in the alloy target is the same as or close to the atomic ratio of the corresponding metal elements in the alloy coating. In some embodiments, the alloy target is a chromium-zirconium-based alloy target, wherein the chromium-zirconium-based alloy target includes at least chromium and zirconium, such as a CrZr alloy target, a CrZrN alloy target, and the like. In some embodiments, the atomic ratio of Cr and Zr in the chromium-zirconium-based alloy target is 65%:35%. In some embodiments, the alloy target includes all the metal elements in the alloy coating. Examples of alloy targets can be found in Example 2 below.

[0247] In the present invention, unless otherwise specified, a "chromium-zirconium-based alloy target" includes at least chromium and zirconium, and may include or exclude other elements. When other elements are included, it is understood that the chemical composition of the target material should generally be within the preset chemical formula (Cr x Zr y N z )M a For example, the chromium-zirconium-based alloy target may be a chromium-zirconium-nitrogen alloy target (ie, a CrZrN alloy target) composed of three elements: chromium, zirconium, and nitrogen.

[0248] In some embodiments, a chromium-zirconium alloy target is used and mounted on Figure 1 The location of Zhongyuan chromium target 4, replace Figure 1 Zhongyuan chromium target 4.

[0249] In some embodiments, the method for preparing the alloy coating, taking a sputtering coating method (such as a magnetron sputtering coating) as an example, comprises the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using a chromium target and a zirconium target or a chromium-zirconium alloy target (i.e., a CrZr alloy target), sputtering and depositing the constituent elements of the alloy coating on at least a portion of the surface of the substrate to form the alloy coating.

[0250] In some embodiments, before the step of "sputtering and depositing the constituent elements of the alloy coating on at least a portion of the surface of the substrate", the following step is also included: cleaning the substrate. The method for cleaning the substrate can adopt a conventional cleaning method in the technical field (including but not limited to the field of decorative plating).

[0251] In some embodiments, the cleaning treatment of the substrate includes the following steps: placing the substrate in water for ultrasonic cleaning for 10-15 minutes, vacuum drying the cleaned substrate for 15-20 minutes, and placing the substrate on a sample stage of a sputtering coating (such as magnetron sputtering coating) device after drying. The sample stage may be a rotatable sample stage.

[0252] In one embodiment, the cleaning process of the substrate includes the following steps: placing the substrate in deionized water (DI water) for ultrasonic cleaning for 10-15 minutes, placing the cleaned substrate in a vacuum baking oven for baking for 15-20 minutes, and placing the substrate on a rotatable sample table in a vacuum chamber after drying.

[0253] In some embodiments, after the step of "cleaning the substrate", and before the step of "sputtering and depositing constituent elements of the alloy coating on at least a portion of the surface of the substrate", the following step is also included: forming a transition layer (the transition layer can serve as a buffer film) on at least a portion of the surface of the cleaned substrate. For example, the constituent elements of the transition layer can be deposited on at least a portion of the surface of the cleaned substrate.

[0254] In some embodiments, after the alloy coating of the present invention is formed on one side of the substrate, further deposition may be performed to form a surface layer, and the surface layer may be a single-layer structure or a multi-layer structure.

[0255] In some embodiments, the temperature of sputtering deposition is 30°C to 330°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 330°C, etc.

[0256] In some embodiments, the total gas pressure of the mixed gas including argon gas and nitrogen-containing gas is 0.3 Pa to 1.2 Pa, for example, 0.3 Pa, 0.5 Pa, 0.8 Pa, 1 Pa, 1.2 Pa, etc.

[0257] In some embodiments, sputtering is performed by radio frequency assisted direct current sputtering, which can further improve the performance of the alloy coating formed by sputtering deposition compared to other preparation methods.

[0258] In some embodiments, the target material includes a chromium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 , optional 1.3W / cm 2 ~6.0W / cm 2 .

[0259] In some embodiments, the target material comprises a zirconium target, and the power density of the zirconium target is 0.5 W / cm 2 ~7.9W / cm 2 , optional 1.5W / cm 2 ~7.9W / cm 2 .

[0260] The target material may include a combination of a chromium target and a zirconium target.

[0261] In some embodiments, the target material comprises an alloy target, and the alloy target comprises at least two metal elements in the alloy coating; optionally, the target material comprises a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2 ~6W / cm 2 .

[0262] In some embodiments, the target material includes the chromium-zirconium alloy target, and the power density of the chromium-zirconium alloy target is 5 W / cm 2 .

[0263] In some embodiments, the target material is a chromium-zirconium alloy target with a power density of 4 W / cm 2 ~6W / cm 2 , 5W / cm2 is optional 2 .

[0264] In some embodiments, the bias voltage of the substrate is -150 V to -20 V, such as -150 V, -120 V, -100 V, -90 V, -80 V, -60 V, -50 V, -40 V, -30 V, -20 V, etc.

[0265] In some embodiments, the gas flow rate of the nitrogen-containing gas may be 5 sccm to 52 sccm, such as 5 sccm, 10 sccm, 20 sccm, 25 sccm, 30 sccm, 40 sccm, 50 sccm, 52 sccm, etc. Further, the nitrogen-containing gas is nitrogen gas.

[0266] In some embodiments, the sputtering deposition time is 10 min to 150 min, for example, 10 min, 15 min, 30 min, 45 min, 60 min, 90 min, 100 min, 120 min, etc. The thickness of the alloy coating of the present invention can be controlled by adjusting the deposition time. As the deposition time increases, the thickness of the alloy coating of the present invention increases.

[0267] In some embodiments, the deposition time is 120 min, and the thickness of the alloy coating is 1.0 μm.

[0268] In some embodiments, the nitrogen-containing gas is nitrogen, and the gas ratio of argon to nitrogen in the mixed gas is (2-6):1, such as 2:1, 3:1, 4:1, 5:1, 6:1, etc. When nitrogen is selected as the nitrogen-containing gas and the nitrogen content is controlled to a certain level, the performance of the alloy coating of the present invention can be further adjusted.

[0269] In some embodiments, the background vacuum of the vacuum chamber used is ≤5.0×10 -4 Pa. This pressure setting can ensure the collision between the sputtered particles and the gas molecules, and can also reduce the entry of impurities into the gas molecules during the deposition process, so as to improve the corrosion resistance, purity and bonding strength of the alloy coating of the present invention.

[0270] It is understandable that argon gas and nitrogen-containing gas can be introduced into the vacuum chamber through a single path or mixed through a mixing cylinder and then enter the chamber, thereby reducing the impurity content of the alloy coating of the present invention and improving its performance.

[0271] In some embodiments, "using sputtering coating (such as magnetron sputtering coating) technology to load the constituent elements of the alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio" includes the following steps: introducing a mixed gas containing argon and nitrogen-containing gas into the vacuum chamber 1, maintaining the pressure in the vacuum chamber 1 at 0.3Pa-1.2Pa, turning on the bias voltage and setting it to -150V to -20V, setting the power density of the Cr target 4 to 1.3W / cm 2 -6.7W / cm 2 , the power density of Zr target 5 was set to 0.5 W / cm 2 -7.9W / cm 2 , a Cr-Zr-N alloy coating is deposited on at least a portion of the surface of the substrate after cleaning; further, the Cr-Zr-N alloy coating with different film thicknesses can be obtained by controlling the film forming time.

[0272] Some specific embodiments are provided below.

[0273] The embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are preferably referred to the guidance provided in the present invention, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0274] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0275] Test method:

[0276] 1. Analysis of morphology and composition of alloy coating

[0277] The samples to be tested all use silicon wafers as substrates.

[0278] Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) testing methods

[0279] Morphology analysis: A scanning electron microscope (Regulus 8230, manufactured by Hitachi) was used.

[0280] Composition analysis: An energy dispersive X-ray spectrometer (EDX) attached to a Regulus 8230 scanning electron microscope produced by Hitachi was used, and the relative intensities of all elements were corrected by the ZAF method.

[0281] Test parameters: the electron acceleration voltage is 15 kilovolts, the beam current is 10 microamperes, the sample magnification is 200 times, and 10 points are tested for each sample to take the average value.

[0282] 2. X-ray diffraction (XRD) test of alloy coating

[0283] When conducting XRD testing of alloy coatings, silicon wafers were used as substrates.

[0284] 2.1. Calculate the half-height width of the diffraction peak in the XRD pattern

[0285] A German Bruker D8 Advance XRD diffractometer was used in the θ-2θ mode with Cu target Kα rays, a wavelength λ of 0.15406 nm, the X-ray tube controlled at 40 kV and 40 mA, a scanning range of 20° to 80°, and precise scanning measurements with a step size of 0.01°.

[0286] The steps for obtaining the half-width value are as follows: first, the diffraction peak is corrected, including: smoothing, background subtraction, removal of Kα2 line, subtraction of instrument broadening, etc., and the half-width value of the diffraction peak is obtained after fitting the diffraction peak with the Pseudo-Voigt function.

[0287] The EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and microanalysis, The university of Sydney) was used to process the spectrum data: first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and then converted into an XRD spectrum (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak was deducted from the straight line background, and then fitted with the Voigt function to obtain the half-height width of the corresponding diffraction peak.

[0288] 2.2. Determine whether the XRD pattern of the alloy coating forms a broad peak

[0289] Method for judging whether there are broad peaks (sharp peaks) in the diffraction angle range of 2θ (°) from 30° to 50° in the XRD diffraction pattern: in the XRD spectrum, if the half-height width of the 2θ (°) diffraction peak is ≥2°, it is judged as a broad peak; if the half-height width of the 2θ (°) diffraction peak is <2°, it is judged as a sharp peak.

[0290] For a given 2θ(°) position, it can be any of the three states: no peak, sharp peak or broad peak.

[0291] 3. TEM test

[0292] When conducting TEM tests on alloy coatings, silicon wafers were used as substrates.

[0293] 3.1. The half-width at half maximum of the diffraction ring of the TEM diffraction pattern is obtained by the following method:

[0294] TEM test sample preparation: The Helios 5 CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.

[0295] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) produced by Thermo Fisher Scientific Inc., USA, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm, was used to obtain the selected area electron diffraction pattern (SAED) of the sample.

[0296] Acquisition of radial intensity profile: The SAED spectrum data obtained above were processed using EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and microanalysis, The university of Sydney): first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and finally, it was converted into a radial intensity profile (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers), with the characteristic atomic spacing as the horizontal axis and the diffraction intensity as the vertical axis.

[0297] The steps for obtaining the half-width value are as follows: subtract a straight line from the diffraction peak, and then fit it with the Voigt function to obtain the half-width value of the corresponding diffraction peak.

[0298] 3.2. Determine the radial intensity profile of the TEM selected area electron diffraction pattern Method for whether there is a broad peak in the range: the characteristic atomic distance corresponds to It is judged as a broad peak; the characteristic atomic distance corresponds to For a specific characteristic interatomic distance, it can be any of the three states: no peak, sharp peak or broad peak.

[0299] 4. Salt spray corrosion resistance test of alloy coating

[0300] When the salt spray corrosion resistance test of the alloy coating is carried out, the sample to be tested is a substrate suitable for practical application, and the improvement degree of the corrosion resistance of the substrate by the alloy coating is detected. The surface material of the "substrate suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel, copper sheet.

[0301] The ASTM B117 salt spray test standard is adopted, the pH value of the solution is 6.5-7.2, and the chemical composition of the solution is: sodium chloride (NaCl), deionized water and sodium hydroxide (NaOH).

[0302] 12 hours can be used as a sub-cycle of the salt spray corrosion resistance test.

[0303] The test cycle of alloy coatings prepared on substrates of different materials can be different, for example:

[0304] The test cycle for samples containing aluminum alloy matrix is ​​48h or 24h;

[0305] The test cycle of stainless steel matrix samples is 144h;

[0306] The test cycle of the copper sheet substrate sample is 12h.

[0307] The standard for "passing (OK)" salt spray corrosion resistance test is: after the sample is tested, there is no corrosion, no discoloration, and no rust on the appearance.

[0308] The standard for "failure (NG)" in the salt spray corrosion test is: after the sample is tested, corrosion, discoloration or rust is found on the surface.

[0309] 5. Hardness test of alloy coating

[0310] When testing the hardness of alloy coatings, the sample to be tested adopts a substrate suitable for actual application.

[0311] The surface material of the "substrate suitable for practical application" may include, but is not limited to: aluminum alloy, stainless steel, copper sheet.

[0312] In the following examples, unless otherwise specified, when testing the hardness of the alloy coating, aluminum alloy and stainless steel are used as the substrate, and the alloy coating is deposited on the aluminum alloy and stainless steel using preset preparation parameters to obtain the test sample for testing the hardness of the alloy coating. This is mainly due to the following considerations: During the nanoindentation test, when the probe penetrates the test sample, a strong pressure is formed. At this time, the substrate is required to have a certain toughness. If a silicon wafer with greater brittleness is used, cracking may occur during the test, resulting in inaccurate test results. Alloy materials are more suitable as the substrate to be tested for nanoindentation testing due to their excellent toughness. Using alloy materials as the substrate to measure the hardness of the coating is universal in the field of coatings for the characterization of coating hardness.

[0313] The hardness of each film or coating was tested using a nanoindenter model NHT3 produced by Anton-Paar, Austria. It was equipped with a tetrahedral Berkvich indenter, and the indentation depth was set to 100 nm. The load changed with the indentation depth. Five matrix points were tested for each sample and the average value was taken.

[0314] 6. Chroma value test of alloy coating

[0315] When testing the chromaticity value of the alloy coating, the sample to be tested uses a substrate material that is suitable for practical application, and detects the degree of improvement of the density and other properties of the substrate by the alloy coating. The surface material of the "substrate that is suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel.

[0316] The L value, a value and b value of the samples were tested using a CM-3700A-U desktop spectrophotometer produced by Konica Japan. The F2 light source was selected as the light receiving system. Six matrix points were tested for each sample and the average value was taken.

[0317] Among them, L value represents the brightness value, a value represents the red and green chromaticity values, and b value represents the -_ yellow and blue chromaticity values.

[0318] The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: the spectrophotometer reflects the incident light on the surface of the sample to be tested, and a reflectance curve is obtained. The amplitude of the curve can reflect the density of the material, which can be specifically characterized by the L value. For the same material, the higher its density, the larger the L value it displays.

[0319] In the following examples, DI water means deionized water.

[0320] The stainless steel sheets, aluminum alloy sheets and silicon sheets in the following embodiments and comparative examples are made of the same material.

[0321] In the following examples, the target material was sputtered by RF-assisted DC sputtering.

[0322] In the following examples, the reference to “there is only one broad peak” in the XRD diagram and the SAED-radial intensity profile diagram, unless otherwise specified, means there is only one characteristic peak, and the peak is a broad peak.

[0323] Example 1.

[0324] In this example, the chemical composition of the alloy coating is Cr 81.6 Zr 13.7 N 4.7 .

[0325] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0326] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0327] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 5 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 6:1, the pressure in the furnace was maintained at 0.6Pa, the bias voltage was turned on and set to -100V, and the power density of the Cr target was set to 6W / cm 2, the power density of the Zr target was set to 1.5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 1300nm.

[0328] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0329] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 81.6 Zr 13.7 N 4.7 .

[0330] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 13.7GPa, and the hardness value of the stainless steel substrate sample is 14.6GPa.

[0331] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Figure 3 , XRD diffraction patterns, TEM-SAED patterns and radial intensity profiles can be found at Figure 4 The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 9.11° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0332] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 81.31, a: 0.26, b: 2.88, and the chroma value of the stainless steel substrate sample tested is L: 82.30, a: 0.20, b: 2.45, which is silvery white in color.

[0333] Example 2.

[0334] In this example, the chemical composition of the alloy coating is Cr 61.4 Zr 33.2 N 5.4 , the preparation method is as follows:

[0335] In this embodiment, the target material is a chromium-zirconium alloy target. Figure 1The original Cr target at the position of the middle chromium target 4 is replaced with a CrZr alloy target with an atomic percentage of Cr and Zr of 65%:35%.

[0336] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, room temperature (about 30°C), maintain for 15 minutes.

[0337] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0338] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to draw power to the CrZr alloy target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 7 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 6:1, the pressure in the furnace was maintained at 0.7 Pa, the bias voltage was turned on and set to -100 V, and the power density of the CrZr alloy target was set to 5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and by controlling the film forming time, the resulting film thickness is made to be 2500nm.

[0339] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0340] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 61.4 Zr 33.2 N 5.4 .

[0341] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 15.1GPa, and the hardness value of the stainless steel substrate sample is 16.3GPa.

[0342] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Figure 5 , XRD diffraction patterns, TEM-SAED patterns and radial intensity profiles can be found at Figure 6The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the half-width of the 2θ(°) diffraction angle in the XRD diffraction pattern within the range of 30° to 50° satisfies ≥2°, and there is only one broad peak with a half-width of 8.85° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0343] The chromaticity value of the aluminum alloy substrate sample tested is L: 79.05, a: 0.43, b: 3.54, and the chromaticity value of the stainless steel substrate sample tested is L: 81.74, a: 0.33, b: 3.04, which is silvery white in color.

[0344] Example 3.

[0345] In this example, the chemical composition of the alloy coating is Cr 47.1 Zr 17.4 N 35.5 , the preparation method is as follows:

[0346] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0347] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0348] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 42 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 2:1, the pressure in the furnace was maintained at 0.8 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 3.9 W / cm 2 , the power density of the Zr target was set to 1.9 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1600nm.

[0349] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0350] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 47.1 Zr 17.4 N 35.5 .

[0351] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 18.2GPa, and the hardness value of the stainless steel substrate sample is 20.4GPa.

[0352] The SEM cross-section test was performed on the test sample, and the cross-sectional morphology was as follows: Figure 7 , XRD diffraction pattern as Figure 8 The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°, and the half-height width of all 2θ(°) peaks in the range of 30° to 50° is ≥2°, among which there is only one broad peak with a half-height width of 4.42° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0353] The chromaticity value of the aluminum alloy substrate sample tested is L: 73.92, a: 0.43, b: 4.78, and the chromaticity value of the stainless steel substrate sample tested is L: 75.50, a: 0.36, b: 4.69, showing bright silver-white color.

[0354] Example 4.

[0355] In this example, the chemical composition of the alloy coating is Cr 52.0 Zr 12.1 N 35.9 , the preparation method is as follows:

[0356] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heated to 150°C, kept constant for 15 minutes;

[0357] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0358] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 42 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 2:1, the pressure in the furnace was maintained at 0.8 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 4.1 W / cm 2 , the power density of the Zr target was set to 1.5 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1700nm.

[0359] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0360] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 52.0 Zr 12.1 N 35.9 .

[0361] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 16.7GPa, and the hardness value of the stainless steel substrate sample is 19.2GPa.

[0362] The SEM cross-section test was performed on the test sample, and the cross-sectional morphology was as follows: Fig. 9 , XRD diffraction pattern as Fig.10 The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of all 2θ(°) peaks in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 4.04° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0363] The chromaticity value of the aluminum alloy substrate sample tested is L: 74.16, a: 0.47, b: 4.00, and the chromaticity value of the stainless steel substrate sample tested is L: 75.70, a: 0.41, b: 3.95, which is silvery white in color.

[0364] Example 5.

[0365] In this example, the chemical composition of the alloy coating is Cr 60.9 Zr 26.1 N 13 , the preparation method is as follows:

[0366] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0367] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0368] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 14 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 3:1, the pressure in the furnace was maintained at 0.7 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.

[0369] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0370] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 60.9 Zr 26.1 N 13 .

[0371] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 11.8GPa, and the hardness value of the stainless steel substrate sample is 13.7GPa.

[0372] The SEM cross-section test was performed on the test sample, and the cross-sectional morphology was as follows: Fig.11 , XRD diffraction patterns, TEM-SAED patterns and radial intensity profiles can be found at Fig.12 The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°, and the half-height width of all 2θ(°) peaks in the range of 30° to 50° in the XRD diffraction pattern is ≥2°, among which there is only one broad peak with a half-height width of 9.33° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0373] The chromaticity value of the aluminum alloy substrate sample tested is L: 79.21, a: 0.41, b: 3.91, and the chromaticity value of the stainless steel substrate sample tested is L: 79.95, a: 0.33, b: 3.73, showing bright silver-white color.

[0374] Example 6.

[0375] In this example, a double-layer film structure is attached to the substrate surface, including a chemical composition of Cr 60.9 Zr 26.1 N 13 The double-layer film structure is denoted as Cr-Zr-N / TiN. At this time, a multi-layer film structure is attached to the surface of the substrate, wherein the alloy coating provided by the present application is used as an intermediate layer, located between the substrate and the surface layer. The preparation method is as follows:

[0376] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0377] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0378] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 14 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 3:1, the pressure in the furnace was maintained at 0.7 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.

[0379] Deposition of surface layer (second coating): Replace the Zr target in the furnace with a Ti target, turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 10 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 3:1, the pressure in the furnace was maintained at 0.5Pa, the bias voltage was turned on and set to -100V, and the power density of the Ti target was set to 5W / cm 2 , TiN coating is deposited, and by controlling the film formation time, the obtained film thickness is 100nm.

[0380] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0381] After component analysis, the component is Cr 60.9 Zr 26.1 N 13 The alloy coating is provided with a TiN coating on the surface.

[0382] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 11.7GPa, and the hardness value of the stainless steel substrate sample is 14.2GPa.

[0383] The SEM cross-section test was performed on the test sample, and the cross-sectional morphology was as follows: Fig.13 The SEM test results show that the alloy coating has a dense structure.

[0384] It should be noted that Fig.13The vertical cracks in the SEM morphology image correspond to the cracks generated in the process of breaking the silicon wafer, and are not column cracks caused by the growth of Cr-Zr-N film.

[0385] The chromaticity value of the aluminum alloy substrate sample tested is L: 58.85, a: 6.65, b: 12.85, and the chromaticity value of the stainless steel substrate sample tested is L: 59.83, a: 6.82, b: 13.61, showing a golden color. The test results here are the chromaticity values ​​of the surface layer TiN.

[0386] Example 7.

[0387] In this example, a three-layer film structure is attached to the substrate surface, which includes a transition layer (as a bottom coating), an alloy coating containing a Cr-Zr-N alloy material, and a second coating located on the surface. The three-layer film structure is recorded as Cr / Cr-Zr-N / TiN, where the transition layer is a Cr layer and the chemical composition of the alloy coating is Cr. 60.9 Zr 26.1 N 13 , the chemical composition of the second coating is TiN. The preparation method is as follows:

[0388] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0389] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0390] Deposition of bottom coating (transition layer): Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target, introduce Ar, set the Ar gas volume to 42 sccm, maintain the furnace pressure at 0.5 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , deposit a Cr base coating, and by controlling the film formation time, the resulting film thickness is 300nm.

[0391] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 14 sccm, and the gas volume is set to maintain Ar:N2 The gas volume ratio was 3:1, the pressure in the furnace was maintained at 0.7 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.

[0392] Deposition of surface layer (second coating): Replace the Zr target in the furnace with a Ti target, turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 10 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 3:1, the pressure in the furnace was maintained at 0.5Pa, the bias voltage was turned on and set to -100V, and the power density of the Ti target was set to 5W / cm 2 , depositing TiN coating, by controlling the film forming time, the obtained film thickness is 100nm;

[0393] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0394] According to the composition analysis, there are three layers of film structure on the surface of the substrate, and the chemical composition is Cr (transition layer), Cr 60.9 Zr 26.1 N 13 (alloy coating of the present application) and TiN (second coating), the three-layer film structure is Cr / Cr-Zr-N / TiN.

[0395] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 13.2GPa, and the hardness value of the stainless steel substrate sample is 15.1GPa.

[0396] The SEM cross-section test was performed on the test sample. Fig.14 The SEM test results show that the alloy coating has a dense structure.

[0397] It should be noted that Fig.14 The vertical cracks in the SEM morphology image correspond to the cracks generated in the process of breaking the silicon wafer, and are not column cracks caused by the growth of Cr-Zr-N film.

[0398] The chromaticity value of the aluminum alloy substrate sample tested is L: 56.64, a: 7.07, b: 14.11, and the chromaticity value of the stainless steel substrate sample tested is L: 58.73, a: 7.35, b: 14.35, showing a golden color. The test results here are the chromaticity values ​​of the surface layer TiN.

[0399] Example 8.

[0400] In this example, the chemical composition of the alloy coating is Cr 60.9 Zr 26.1 N 13 , the preparation method is as follows:

[0401] Pretreatment: The copper and silicon wafer samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven, and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0402] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0403] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 14 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 3:1, the pressure in the furnace was maintained at 0.7 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.

[0404] The samples using copper sheets as the substrate were subjected to salt spray corrosion resistance test, hardness test and chromaticity value test, and the samples using silicon sheets as the substrate were subjected to SEM and composition analysis, XRD analysis and TEM test.

[0405] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 60.9 Zr 26.1 N 13 .

[0406] In the salt spray corrosion test, the copper substrate sample can pass the 12h test and has certain protective properties. The hardness value of the copper substrate sample is 7.9GPa.

[0407] The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that there is a broad peak in the XRD diffraction pattern, and the half-height width of the 2θ(°) diffraction angle in the range of 30° to 50° is ≥2°, among which there is only one broad peak with a half-height width of 9.33° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0408] The chromaticity values ​​of the copper substrate sample tested were L: 80.15, a: 0.53, b: 4.63, showing a bright silver-white color.

[0409] Example 9.

[0410] In this embodiment, the chemical composition of the alloy coating is Cr 15.0 Zr 78.8 N 6.2 , the preparation method is as follows:

[0411] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0412] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0413] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 8 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 6:1, the pressure in the furnace was maintained at 0.7 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 1.3 W / cm 2 , the power density of the Zr target was set to 7.9 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 2500nm.

[0414] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0415] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 15.0 Zr 78.8 N 6.2 .

[0416] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 20.6GPa, and the hardness value of the stainless steel substrate sample is 22.8GPa.

[0417] The SEM cross-section test of the test sample, the cross-sectional morphology and TEM-SAED map and radial strength profile can be found in Fig.15 According to the test results, the alloy structure is dense, and no through-column cracks are observed; the XRD test results show that there is a broad peak in the XRD diffraction pattern, and the half-height width of the 2θ(°) diffraction angle in the range of 30° to 50° is ≥2°, among which there is only one broad peak with a half-height width of 3.92° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0418] The chromaticity value of the aluminum alloy substrate sample tested is L: 74.29, a: 0.53, b: 6.38, and the chromaticity value of the stainless steel substrate sample tested is L: 75.65, a: 0.47, b: 6.31, which is silvery white in color.

[0419] Example 10.

[0420] In this embodiment, the chemical composition of the alloy coating is Cr 15.0 Zr 49.5 N 35.5 , the preparation method is as follows:

[0421] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0422] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0423] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 42 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 2:1, the pressure in the furnace was maintained at 0.8 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 1.3 W / cm 2 , the power density of the Zr target was set to 5 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 2200nm.

[0424] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0425] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 15.0 Zr 49.5 N 35.5 .

[0426] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 21.2GPa, and the hardness value of the stainless steel substrate sample is 22.6GPa.

[0427] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.16 , XRD diffraction patterns, TEM-SAED patterns and radial intensity profiles can be found at Fig.17 . The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed. The XRD test results show that there is a broad peak in the XRD diffraction pattern, and the half-width of the 2θ(°) diffraction angle in the range of 30° to 50° is ≥2°, among which there is only one broad peak with a half-width of 2.23° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0428] The chromaticity value of the aluminum alloy substrate sample tested is L: 75.25, a: 0.52, b: 6.48, and the chromaticity value of the stainless steel substrate sample tested is L: 76.95, a: 0.41, b: 6.04, showing bright silver-white color.

[0429] Example 11.

[0430] In this embodiment, the chemical composition of the alloy coating is Cr 41.3 Zr 33.2 N 25.5 , the preparation method is as follows:

[0431] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0432] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0433] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to draw power to the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 33 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 2:1, the pressure in the furnace was maintained at 0.7 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 3.8 W / cm 2 , the power density of the Zr target was set to 3 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 2500nm.

[0434] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0435] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 41.3 Zr 33.2 N 25.5 .

[0436] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 17.2GPa, and the hardness value of the stainless steel substrate sample is 18.8GPa.

[0437] The SEM test results show that the alloy coating has a dense structure and no through-holes are observed. The test results of XRD diffraction patterns, TEM selected area electron diffraction patterns and radial intensity profiles can be found at Fig.18 The XRD test results show that the XRD diffraction pattern has a broad peak, and the half-width of the 2θ(°) diffraction angle in the range of 30° to 50° is ≥2°, among which there are two broad peaks with half-width of 6.05° and 5.54° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0438] The chromaticity value of the aluminum alloy substrate sample tested is L: 75.01, a: 0.82, b: 5.52, and the chromaticity value of the stainless steel substrate sample tested is L: 77.16, a: 0.64, b: 4.99, which is silvery white in color.

[0439] Example 12. The alloy coating thickness is 50 nm.

[0440] The same method as in Example 5 was used, and the chemical composition of the Cr-Zr-N alloy coating was Cr 60.9 Zr 26.1 N 13.0 , the only difference is that the thickness of the alloy coating is adjusted to 50nm.

[0441] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 8.2GPa, and the hardness value of the stainless steel substrate sample is 9.7GPa.

[0442] The chromaticity value of the aluminum alloy substrate sample tested is L: 80.11, a: 0.41, b: 3.61, and the chromaticity value of the stainless steel substrate sample tested is L: 80.95, a: 0.34, b: 3.43, showing bright silver-white color.

[0443] Example 13. Alloy coating thickness is 6 μm

[0444] The same method as in Example 5 was used, and the chemical composition of the Cr-Zr-N alloy coating was Cr 60.9 Zr 26.1 N 13.0, the only difference is that the thickness of the alloy coating is adjusted to 6000nm.

[0445] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 22.8GPa, and the hardness value of the stainless steel substrate sample is 24.7GPa.

[0446] The chromaticity value of the aluminum alloy substrate sample tested is L: 77.31, a: 0.45, b: 3.81, and the chromaticity value of the stainless steel substrate sample tested is L: 76.94, a: 0.34, b: 3.83, showing bright silver-white color.

[0447] Example 14. Containing doping elements

[0448] In this embodiment, the chemical composition of the alloy coating containing doping elements is Cr 47.1 Zr 17.4 N 30.5 C 5 At this time, the sum of the atomic ratios of Cr, Zr, and N is normalized to 100, and the atomic ratios of Cr, Zr, and N are approximately 49.579:18.316:32.105, and the atomic percentage of the doping element C in the Cr-Zr-N alloy coating is 5%. The preparation method is as follows:

[0449] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0450] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0451] Deposition of the alloy coating of this application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use radio frequency assisted DC power supply to draw power for the Cr target and Zr target, and introduce Ar and C 2 H 2 and N 2 Gas, N 2 The gas flow rate was set to 35 sccm, C 2 H 2 The gas flow rate is set to 6 sccm, and the gas volume is set to maintain Ar: (C 2 H 2 +N 2) gas volume ratio was 2:1, the furnace pressure was maintained at 0.8Pa, the bias voltage was turned on and set to -100V, and the power density of the Cr target was set to 3.9W / cm 2 , the power density of the Zr target was set to 1.9 W / cm 2 , depositing the Cr-Zr-NC alloy coating of the present application (specifically a carbon-doped Cr-Zr-N alloy coating), and by controlling the film forming time, the obtained film thickness is 1600nm.

[0452] Stainless steel sheets and aluminum alloy sheets were used as substrate samples for salt spray corrosion resistance tests, hardness tests and chromaticity tests.

[0453] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 47.1 Zr 17.4 N 30.5 C 5 .

[0454] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 18.9GPa, and the hardness value of the stainless steel substrate sample is 20.4GPa.

[0455] The chromaticity value of the aluminum alloy substrate sample tested is L: 72.72, a: 0.41, b: 4.58, and the chromaticity value of the stainless steel substrate sample tested is L: 73.81, a: 0.38, b: 4.27, which is bright silver-white in color.

[0456] According to the experimental exploration results of the inventors, when other non-metallic doping elements (such as Si, B, O, etc.) or metal doping elements (such as Al) are used, when the atomic ratio of the doping elements is appropriate (such as 4at%, 2at%), excellent corrosion resistance and high hardness can also be provided. In some embodiments, in the salt spray corrosion resistance test experiment, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test. It can also have at least one broad peak in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diffraction pattern, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range.

[0457] "at%" means atomic percent, by number.

[0458] Example 15.

[0459] In this embodiment, the chemical composition of the alloy coating is Cr 49.5 Zr 18.0 N 32.5The preparation method is as follows:

[0460] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0461] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0462] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use radio frequency assisted DC power supply to draw power for the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 42 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 2:1, the pressure in the furnace was maintained at 0.8 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 4.7 W / cm 2 , the power density of the Zr target was set to 1.8 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1600nm.

[0463] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test, and silicon wafers were used as the matrix samples for composition analysis, XRD analysis and TEM test.

[0464] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 49.5 Zr 18.0 N 32.5 .

[0465] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 18.5GPa, and the hardness value of the stainless steel substrate sample is 19.4GPa.

[0466] The test results of XRD diffraction spectrum, TEM selected area electron diffraction pattern and radial intensity profile can be found at Fig.19The diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of all 2θ(°) peaks in the range of 30°~50° in the XRD diffraction pattern is greater than 2°, among which there is only one broad peak with a half-height width of 2.19° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0467] The chromaticity value of the aluminum alloy substrate sample tested is L: 74.52, a: 0.41, b: 4.48, and the chromaticity value of the stainless steel substrate sample tested is L: 75.70, a: 0.32, b: 4.39, showing bright silver-white color.

[0468] In addition, the inventors of the present application have found through a large number of experimental explorations that for the alloy coating containing Cr, Zr and N provided in the present application, when the following two conditions are met at the same time: (1) the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and (2) the radial intensity profile of the TEM selected area electron diffraction pattern is The prepared Cr-Zr-N alloy coating has excellent corrosion resistance and high hardness characteristics. If only the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50° and the radial intensity profile in the TEM-SAED pattern is If there is no broad peak in the range, the prepared Cr-Zr-N alloy coating may have poor corrosion resistance. For example, the corresponding aluminum alloy substrate sample may not pass the 24h salt spray corrosion test. The XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, while the diffraction angle 2θ (°) in the XRD diffraction pattern has no broad peak in the range of 30° to 50°, which may also lead to poor corrosion resistance of the Cr-Zr-N alloy coating. Please refer to the following Comparative Example 4.

[0469] In addition to the above embodiments, the inventors also prepared the following Cr-Zr-N alloy coating with "highly disordered and fully densely packed" structural characteristics, the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is The prepared alloy coating has excellent corrosion resistance and high hardness. In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, and has excellent protective properties. These embodiments include: (1) The component is Cr 53.8 Zr 40.0 N 6.2The alloy coating has a broad peak with a half-height width of 8.42° in the XRD diffraction pattern with a diffraction angle 2θ(°) in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is a broad peak in the range, and the half-height width is The hardness value of the aluminum alloy substrate sample tested is 16.1 GPa, and the hardness value of the stainless steel substrate sample tested is 18.3 GPa. (2) The component is Cr 548 Zr 351 N 101 The alloy coating has a broad peak with a half-height width of 9.25° in the XRD diffraction pattern with a diffraction angle 2θ(°) in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is a broad peak in the range, and the half-height width is The hardness value of the aluminum alloy substrate sample tested is 15.9 GPa, and the hardness value of the stainless steel substrate sample tested is 17.8 GPa. (3) The component is Cr 34.5 Zr 30.0 N 35.5 The alloy coating has a broad peak with a half-height width of 3.52° in the XRD diffraction pattern with a diffraction angle 2θ(°) in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is a broad peak in the range, and the half-height width is The hardness value of the aluminum alloy substrate sample tested was 21.7 GPa, and the hardness value of the stainless steel substrate sample tested was 22.1 GPa.

[0470] Comparative Example 1.

[0471] In this comparative example, the chemical composition of the alloy coating is Cr 88.9 Zr 11.1 , the preparation method is as follows:

[0472] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0473] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0474] Deposition of Cr-Zr alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar gas, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage and set it to -100 V, and set the power density of the Cr target to 6.7 W / cm 2 , the power density of the Zr target was set to 0.8 W / cm 2 , deposited Cr-Zr alloy coating, and by controlling the film forming time, the obtained film thickness was 1900nm.

[0475] Stainless steel sheets and aluminum alloy sheets were used as substrate samples for salt spray corrosion resistance tests, hardness tests and chromaticity value tests. Silicon wafers were used as substrate samples for SEM and composition analysis tests.

[0476] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 88.9 Zr 11.1 .

[0477] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), with poor protection properties. The hardness value of the aluminum alloy substrate sample was 18.5GPa, and the hardness value of the stainless steel substrate sample was 19.6GPa.

[0478] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig. 20 The SEM test results show that the alloy coating film has crystal defects, a loose structure, and obvious gaps.

[0479] The chromaticity value of the aluminum alloy substrate sample tested is L: 83.21, a: -0.21, b: 0.88, and the chromaticity value of the stainless steel substrate sample tested is L: 85.05, a: -0.25, b: 0.79, which is silvery white in color.

[0480] Comparative Example 2.

[0481] In this comparative example, the chemical composition of the alloy coating is Cr 37.8 Zr 16.2 N 46 , the preparation method is as follows:

[0482] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0483] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0484] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use radio frequency assisted DC power supply to draw power for the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate was set to 52 sccm, and the gas volume was set to maintain Ar:N 2 The gas volume ratio was 2:1, the pressure in the furnace was maintained at 0.9 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 3.5 W / cm 2 , the power density of the Zr target was set to 1.8 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.

[0485] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0486] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 37.8 Zr 16.2 N 46 .

[0487] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), and the protection characteristics were poor. The hardness value of the aluminum alloy substrate sample was 16.6GPa, and the hardness value of the stainless steel substrate sample was 18.1GPa.

[0488] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.21 The test results of XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile can be found at Fig. 22 . The SEM test results show that the alloy coating film has a loose structure and obvious through-column cracks. The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has two peaks in the range of 30° to 50°, and they are two sharp peaks (2θ peaks with a half-height width value of <2°). Among them, the half-height widths of the two peaks in the range of 30° to 50° are 0.66° and 1.24° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there are two peaks.

[0489] The chromaticity value of the aluminum alloy substrate sample tested is L: 61.87, a: 0.57, b: 4.45, and the chromaticity value of the stainless steel substrate sample tested is L: 67.38, a: 0.49, b: 4.29. The color is dull and does not have a metallic color.

[0490] Comparative Example 3.

[0491] In this comparative example, the thin film structure of the alloy coating is TiN, and the chemical composition of the alloy coating is TiN.

[0492] To prepare the coating of this comparative example, the Zr target in the furnace body was replaced with a Ti target, and the preparation method was as follows:

[0493] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0494] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0495] Deposition of TiN coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 10 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 3:1, the pressure in the furnace was maintained at 0.5Pa, the bias voltage was turned on and set to -100V, and the power density of the Ti target was set to 5W / cm 2 , TiN coating is deposited, and by controlling the film formation time, the obtained film thickness is 200nm.

[0496] Stainless steel sheets and aluminum alloy sheets were used as substrate samples for salt spray corrosion resistance tests, hardness tests and chromaticity tests.

[0497] The composition analysis showed that the alloy coating on the substrate surface was composed of TiN.

[0498] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h). The hardness value of the aluminum alloy substrate sample was 3.8GPa, and the hardness value of the stainless steel substrate sample was 4.3GPa.

[0499] The chromaticity value of the aluminum alloy substrate sample tested is L: 57.95, a: 6.45, b: 13.95, and the chromaticity value of the stainless steel substrate sample tested is L: 59.33, a: 6.92, b: 13.91, which is golden in color.

[0500] Comparative Example 4.

[0501] In this comparative example, the chemical composition of the alloy coating is Cr 39.6 Zr 19.4 N 41 , the preparation method is as follows:

[0502] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0503] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0504] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use radio frequency assisted DC power supply to draw power for the Cr target and Zr target, and introduce Ar and N 2 Gas, N 2 The gas flow rate is set to 45 sccm, and the gas volume is set to maintain Ar:N 2 The gas volume ratio was 2:1, the pressure in the furnace was maintained at 0.8 Pa, the bias voltage was turned on and set to -100 V, and the power density of the Cr target was set to 4.6 W / cm 2 , the power density of the Zr target was set to 2.2 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1400nm.

[0505] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0506] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 39.6 Zr 19.4 N 41 .

[0507] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 15.4GPa, and the hardness value of the stainless steel substrate sample was 17.2GPa.

[0508] The SEM test results show that the alloy coating film has crystal defects, the structure is not dense, and there are obvious through-column gaps. The test results of XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile can be found in Fig.23 The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has two peaks in the range of 30° to 50° and both are sharp peaks (2θ peaks with half-height width values ​​< 2°). Among them, the half-height widths of the two peaks in the range of 30° to 50° are 1.87° and 1.02° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there is one peak.

[0509] The chromaticity value of the aluminum alloy substrate sample tested is L: 64.71, a: 0.58, b: 4.15, and the chromaticity value of the stainless steel substrate sample tested is L: 66.38, a: 0.49, b: 4.27, which is silvery white in color.

[0510] Comparative Example 5. Alloy coating thickness 50nm

[0511] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 50nm.

[0512] The hardness of the aluminum alloy substrate sample was 9.1GPa, and the hardness of the stainless steel substrate sample was 9.8GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0513] Comparative Example 6: Alloy coating thickness 1000nm

[0514] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 1000nm.

[0515] The hardness of the aluminum alloy substrate sample was 16.5GPa, and the hardness of the stainless steel substrate sample was 17.9GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0516] Comparative Example 7: Alloy coating thickness 2500nm

[0517] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 2500nm.

[0518] The hardness of the aluminum alloy substrate sample was 20.5GPa, and the hardness of the stainless steel substrate sample was 21.1GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0519] Comparative Example 8: Alloy coating thickness 6000nm

[0520] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 6000nm.

[0521] The hardness of the aluminum alloy substrate sample was 22.1GPa, and the hardness of the stainless steel substrate sample was 23.7GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0522] Comparative Examples 9-11. No protective coating

[0523] Aluminum alloy bare chips, stainless steel bare chips and copper bare chips were respectively subjected to salt spray corrosion resistance tests. The results showed that obvious corrosion occurred within 12 hours.

[0524] Result analysis:

[0525] According to the results of XRD test and TEM selected area electron diffraction test, the Cr-Zr-N alloy coating (Examples 1-15) provided by the present invention has at least one broad peak (furthermore, all are broad peaks, and the half-height width is ≥2°) in the diffraction peaks of the diffraction angle 2θ (°) in the range of 30° to 50° in the XRD diffraction pattern, and the radial intensity profile of the TEM selected area electron diffraction pattern is ≥2°. There is at least one broad peak in the range (further, all are broad peaks, ), the Cr-Zr-N alloy coatings provided in the present application all have highly disordered atomic distribution and sufficiently densely packed atomic arrangement, which is consistent with the highly dense structure in the SEM morphology characterization results.

[0526] The alloy coatings prepared in Examples 1-15 can be used as the protective coating itself or as a part of the protective coating, and can both provide excellent corrosion resistance and high hardness properties, thereby inhibiting corrosion and resisting scratches and marks.

[0527] According to the test results of salt spray corrosion resistance, the alloy coatings provided by the present invention (Examples 1-15) can bring excellent corrosion resistance to the substrate; wherein Examples 1-5 and 8-15 are single-layer film structures, and the alloy coatings provided by the present invention directly provide surface protection for the substrate; Example 6 is a double-layer film structure, and the alloy coating provided by the present invention serves as a lower protective layer, and a second coating (TiN) is also attached to the surface of the alloy coating on the side away from the substrate, and the second coating serves as a surface protective coating (located on the upper layer); the coating of Example 7 is a three-layer film structure, which includes a transition layer (as a bottom coating), an alloy coating containing a Cr-Zr-N alloy material, and a second coating located on the surface in sequence from the substrate surface; the alloy coating in Example 14 contains a certain atomic percentage of doping elements (≤5at%); Examples 1-7, 9-15 all use aluminum alloy substrates and stainless steel substrates, and Example 8 uses a copper substrate, the aluminum alloy surface can pass the 48h salt spray corrosion resistance test, the stainless steel surface can pass the 144h salt spray corrosion resistance test, and the copper-based (copper is a more active alloy) body can pass the 12h salt spray corrosion resistance test. The alloy coating provided by the present invention can be independently used as a single-layer film, or it can be located in a multi-layer composite film, for example, it can be used as one layer, that is, it can be used as a surface layer (exposed), it can also be used as a bottom coating (contacting the substrate), or it can be used as an intermediate layer (located between the bottom coating and the surface layer).

[0528] The bare substrate chips of Comparative Examples 9-11, without a protective coating, were not resistant to salt spray corrosion and suffered obvious corrosion within 12 hours.

[0529] The alloy coating film of Comparative Example 1 lacks N element, the alloy coating films of Comparative Example 2 and Comparative Example 4 have a high content of N element, and Comparative Example 3 is not provided with the Cr-Zr-N alloy coating of the present invention (Comparative Example 3 is a TiN coating). It is found that Comparative Examples 1-4 all failed the corrosion test (NG). The reason may be that the film structure is not dense and there are gaps, such as penetrating column gaps, which cause the corrosive solution to quickly pass through the gaps and contact the substrate, thereby causing the corrosion resistance of the coating to fail.

[0530] For the alloy coatings of different thicknesses in Comparative Examples 5-8, their hardness and corrosion resistance are significantly inferior to those of the Cr-Zr-N alloy coatings of the present invention of the same thickness. Among them, even though Comparative Example 8 has a thickness of up to 6000nm (6 micrometers), its hardness is high, but its corrosion resistance is still poor. The inventor speculates that the reasons may be: the film structure is not dense, and there are gaps, such as penetrating column gaps, which cause the corrosive solution to quickly pass through the gaps and contact the substrate, thereby causing the corrosion resistance of the coating to fail; increasing the thickness of the coating can increase the hardness of the coating, but the structural defects still exist.

[0531] The Cr-Zr-N alloy coating provided by the present invention can have both excellent corrosion resistance and high hardness characteristics at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. When the thickness of the alloy coating is relatively thin, the formed plated product can present a silvery white metallic color close to the metallic color of the substrate, which is more conducive to achieving a beautiful decorative effect without changing the color of the substrate.

[0532] The technical features of the above-mentioned embodiments and examples can be combined in any appropriate manner. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0533] The above embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solution of the present invention in detail, but it cannot be understood as limiting the scope of protection of the present invention. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several variations and improvements can be made, which all belong to the protection scope of the present invention. In addition, it should be understood that after reading the above teaching content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. It should also be understood that the technical solutions obtained by those skilled in the art on the basis of the technical solution provided by the present invention through logical analysis, reasoning or limited experiments are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the content of the attached claims, and the description and drawings can be used to explain the content of the claims.

Claims

1. An alloy coating, characterized in that: The alloy coating contains a Cr-Zr-N alloy material, and the alloy coating satisfies the following two characteristics: The X-ray diffraction pattern of the alloy coating has a peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak within the range of 30° to 50° satisfies ≥ 2°; In the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating, the characteristic atomic distance is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-height width of at least one diffraction peak in the range satisfies ≥ 2. The alloy coating according to claim 1, characterized in that The X-ray diffraction pattern of the alloy coating satisfies one or more of the following characteristics: The X-ray diffraction pattern of the alloy coating satisfies a half-width of all 2θ(°) diffraction peaks within a diffraction angle 2θ(°) range of 30° to 50° of ≥2°; The X-ray diffraction pattern of the alloy coating is obtained by Cu target Kα radiation.

3. The alloy coating according to claim 1 or 2, characterized in that: The radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating satisfies one or more of the following characteristics: The radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating is The half-height width of all diffraction peaks in the range meets ≥ The selected area electron diffraction pattern of the alloy coating is obtained by using TEM characterization technology, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

4. The alloy coating according to any one of claims 1 to 3, characterized in that The chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , M is a doping element, wherein x, y, z and a are each independently an atomic ratio, 15≤x≤81.6, 12.1≤y≤78.8, 4.7≤z≤35.9, and 0≤a / (x+y+z+a)≤0.

05.

5. The alloy coating according to claim 4, characterized in that The sum of x, y, and z is 100.

6. The alloy coating according to claim 4, characterized in that 0≤a / (x+y+z+a)≤0.

02.

7. The alloy coating according to claim 4, characterized in that The doping element is a non-metallic element, a metallic element or a combination thereof; The non-metallic elements include one or more of O, C, B, Si and Ar; The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

8. The alloy coating according to any one of claims 1 to 3, characterized in that The thickness of the alloy coating is d min nm~6μm, where d min Selected from 10nm to 50nm.

9. The alloy coating according to claim 8, characterized in that d min The thickness of the alloy coating is 10 nm, 20 nm, 25 nm, 30 nm, 40 nm or 50 nm; optionally, the thickness of the alloy coating is 1 μm to 2.5 μm.

10. A coated product, characterized in that: It comprises a substrate and the alloy coating according to any one of claims 1 to 9; wherein the alloy coating is located on at least one side of the substrate.

11. The coated product according to claim 10, characterized in that: The surface material of the substrate is one of alloy, elemental metal and inorganic non-metallic material; The material type of the alloy includes one or more of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based; The elemental metal is any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium; The inorganic non-metallic material includes one or more of ceramics and glass.

12. The coated product according to claim 11, characterized in that: The surface material of the substrate is one of light alloys or one of stainless steel alloys; wherein the light alloy includes one or more of titanium alloy, aluminum alloy and magnesium alloy.

13. The coated product according to claim 10, characterized in that: Satisfy one or more of the following characteristics: The alloy coating is in direct contact with the substrate or is provided with a transition layer; The alloy coating is located on the surface of the coated product or a surface layer is provided on the side of the alloy coating away from the substrate, and the surface layer is a single-layer structure or a multi-layer structure.

14. The coated product according to claim 10, characterized in that: The coated product is one of 3C digital products, automotive products, aerospace products, wearable products and sports products.

15. An alloy coating composition, characterized in that: The alloy coating composition contains a Cr—Zr—N alloy material, and the Cr—Zr—N alloy material is as defined in any one of claims 1 to 7.

16. Use of the alloy coating according to any one of claims 1 to 9 as at least a part of the protective coating of a plated product, or use of the alloy coating composition according to claim 15 in preparing at least a part of the protective coating of a plated product.

17. The use according to claim 16, characterized in that The protective coating of the plated product is a corrosion-resistant protective coating.

18. A method for preparing an alloy coating, characterized in that: The method comprises the following steps: using vapor deposition technology to deposit the constituent elements of the alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio, so as to form the alloy coating as claimed in any one of claims 1 to 9.

19. The preparation method according to claim 18, characterized in that: The preparation method of the alloy coating comprises the following steps: under the condition of introducing a mixed gas comprising argon and nitrogen-containing gas, using one or more target materials comprising chromium and zirconium, sputtering and depositing the constituent elements of the alloy coating on at least a portion of the surface of the substrate to form the alloy coating.

20. The preparation method according to claim 19, characterized in that: Satisfy any one or more of the following characteristics: The temperature of sputtering deposition is 30℃~330℃; The total gas pressure of the mixed gas containing argon gas and nitrogen-containing gas is 0.3Pa to 1.2Pa; The target material includes a chromium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 , optional 1.3W / cm 2 ~6.0W / cm 2 ; The target material includes a zirconium target, and the power density of the zirconium target is 0.5 W / cm 2 ~7.9W / cm 2 , optional 1.5W / cm 2 ~7.9W / cm 2 ; The target material includes an alloy target, and the alloy target includes at least two metal elements in the alloy coating; optionally, the target material includes a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2 ~6W / cm 2 ; The bias voltage of the substrate is -150V to -20V; The sputtering deposition time is 10min to 150min; The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 5 sccm to 52 sccm; The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon and nitrogen in the mixed gas is (2-6):1.